Porous catalyst carrier shaped body
The geometric tortuosity and effective diffusion parameters of the porous catalyst support were determined through FIB-SEM analysis, and its pore structure was optimized, which solved the problem of limited catalyst performance in the prior art, and improved the efficiency and choice of ethylene gas-phase oxidation to prepare ethylene oxide sex.
Patent Information
- Application Number
- CN202180045882.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-06-26
- Filing Date
- 2021-06-25
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2041-06-25
AI Technical Summary
The pore structure of existing porous catalyst support cannot be fully characterized, resulting in limited catalytic performance. Especially in the process of preparing ethylene oxide with gas phase oxidation, the pore structure of the catalyst affects the reaction efficiency and selectivity.
Computer-aided three-dimensional reconstruction using focused ion beam scanning electron microscopy (FIB-SEM) analysis was used to determine the geometric tortuosity and effective diffusion parameters of the porous catalyst support through image analysis algorithm, and optimize the pore structure of the support to improve reaction efficiency.
By optimizing the pore structure, the selectivity and reaction efficiency of the catalyst are improved, unwanted side reactions are reduced, and the mechanical stability and density of the catalyst are improved.
Smart Images

Figure CN115867381B_ABST
Abstract
Description
[0001] The invention relates to porous catalyst support shaped bodies, shaped catalyst bodies for preparing ethylene oxide by gas-phase oxidation of ethylene, a process for preparing shaped catalyst bodies and a process for preparing ethylene oxide by gas-phase oxidation of ethylene.
[0002] Alumina (Al2O3) is commonly found in supports and / or catalysts for many heterogeneous catalytic processes. Some of these catalytic processes occur under conditions of high temperature, high pressure, and / or high steam pressure. Alumina is known to have many crystalline phases, such as alpha-alumina (commonly referred to as α-alumina or α-Al2O3), gamma-alumina (commonly referred to as γ-alumina or γ-Al2O3), and numerous polymorphs of alumina. Alpha-alumina is the most stable at high temperatures but has the lowest surface area.
[0003] Gamma-alumina has a very high surface area. This is generally attributed to the fact that the alumina molecules are in a crystal structure that is not very tightly packed. Gamma-alumina is a so-called activated alumina or transition alumina, as it is one of many aluminas that can be converted into various polymorphs. Unfortunately, when gamma-alumina is heated to high temperatures, the atomic structure collapses, and the surface area decreases significantly. The densest crystalline form of alumina is alpha-alumina.
[0004] Ethylene oxide is produced in large quantities and is primarily used as an intermediate for the preparation of various industrial chemicals. In the industrial oxidation of ethylene to ethylene oxide, heterogeneous catalysts comprising silver deposited on a porous support are generally used. To carry out heterogeneously catalyzed gas-phase oxidations, an oxygen-containing gas, such as air or a mixture of pure oxygen and ethylene, is generally passed through a plurality of tubes arranged in a reactor, in which a packing of shaped catalyst bodies is present.
[0005] Catalyst performance is typically characterized by selectivity, activity, the lifetime of the catalyst's selectivity and activity, and mechanical stability. Selectivity is the mole fraction of converted olefin that produces the desired olefin oxide. Even small improvements in selectivity and maintaining selectivity over longer periods of time can lead to significant advantages in process efficiency.
[0006] In order to effectively utilize the internal surface area of a porous supported catalyst, the feed gas must diffuse through the pores to reach the internal surface area, and the reaction products must diffuse away from these surfaces and out of the catalyst mass. In processes for producing ethylene oxide by gas-phase oxidation of ethylene, diffusion of ethylene oxide molecules from the catalyst mass can be accompanied by undesirable further reactions initiated by the catalyst, such as isomerization to acetaldehyde and subsequent complete combustion to carbon dioxide, which reduces the overall selectivity of the process. The average residence time of the molecules in the pores, and therefore the extent to which undesirable further reactions occur, is influenced by the catalyst's pore structure.
[0007] The catalytic performance is therefore influenced by the pore structure of the catalyst, which in turn depends essentially on the pore structure of the catalyst support. The term "pore structure" is understood to refer to the arrangement of the cavities within the support matrix, including the size, size distribution, shape, and interconnectivity of the pores. This can be characterized by various methods, such as mercury porosimetry, nitrogen physisorption, or tomography. H. Giesche, "Mercury Porosimetry: A General (Practical) Overview," Part. Part. Syst. Charact. 23 (2006), 9–19, provides useful insights into mercury porosimetry.
[0008] EP 2 617 489 A1 describes a catalyst support in which at least 80% of the pore volume is present in pores with a diameter in the range from 0.1 to 10 μm and at least 80% of the pore volume in pores with a diameter in the range from 0.1 to 10 μm is present in pores with a diameter in the range from 0.3 to 10 μm.
[0009] WO 03 / 072244 A1 and WO 03 / 072246 A1 each describe a catalyst support in which at least 70% of the pore volume is present in pores with a diameter of 0.2 to 10 μm, and the pores with a diameter between 0.2 and 10 μm constitute a volume of at least 0.27 mL / g of support.
[0010] EP 1 927 398 A1 describes a catalyst support having a pore size distribution with at least two maxima in the range from 0.01 to 100 μm, at least one of these maxima being in the range from 0.01 to 1.0 μm.
[0011] EP 3 639 923 A1 describes a shaped catalyst body having a multimodal pore size distribution with a maximum in the range of 0.1 to 3.0 μm and a maximum in the range of 8.0 to 100 μm, wherein at least 40% of the total pore volume of the shaped catalyst body comes from pores with a diameter in the range of 0.1 to 3.0 μm.
[0012] WO 2021 / 038027 A1 describes a catalyst for preparing ethylene oxide, which uses a porous aluminum oxide support having a foam-like structure.
[0013] However, characterizing catalyst supports by their pore size distribution—for example, by assigning a fraction of the total pore volume to a range of pore sizes—does not fully characterize the morphology and usability of porous catalyst supports. To accurately characterize the mass transfer through the pores of porous solids, structural parameters of the material, such as porosity, pore tortuosity, and pore contraction, must be determined. In particular, pore size distributions fail to reveal how many tortuosities, convolutions, dead ends, and local variations in cross-section, such as contractions, are present in the channels within the porous medium.
[0014] US 2016 / 0354760 A1 relates to a porous body comprising at least 80% α-alumina and having a pore volume of 0.3 to 1.2 mL / g, a pore volume of 0.3 to 3.0 m 2 / g surface area and a pore structure with a tortuosity of 7 or less, a contraction of 4 or less, and / or a permeability of 30 mD or greater. Tortuosity, contraction, and permeability are calculated from Hg intrusion data. For example, tortuosity ξ is calculated from the following equation, where D avg is the weight-average pore size, k is the permeability, ρ is the true density and I tot is the total specific intrusion volume:
[0015]
[0016] The shrinkage σ is calculated by the following equation, where ξ is the tortuosity and τ is the tortuosity factor:
[0017]
[0018] Exemplary carriers from US 2016 / 0354760 A1 have a shrinkage σ in the range of 1.6 to 5.3.
[0019] Still very much need to improve the property of supported catalyst by the structure of optimizing alumina-based carrier.Carrier structure should have high total pore volume, so that might use a large amount of silver impregnation, and surface area should keep high enough to guarantee catalytic activity species, especially the best dispersion of metal species simultaneously.The pore structure that brings the maximum mass transfer rate in the carrier is also ideal, so that the average pore residence time of reactant and product molecules is minimized and the degree that the primary reaction product such as ethylene oxide takes place when they pass through the pore diffusion of supported catalyst is unwanted secondary reaction.In addition, despite having the described requirement to high pore volume and being enough to the pore structure of high rate mass transfer in pore, this supported shaped catalyst body should have high density and high mechanical strength in the filling tube.
[0020] The present invention relates to a porous catalyst support shaped body comprising at least 85% by weight of alpha-aluminum oxide, wherein the support has a total pore volume in the range of 0.5 to 2.0 mL / g as determined by mercury porosimetry, and a pore structure characterized by
[0021] - a geometric tortuosity τ in the range of 1.0 to 2.0; and
[0022] - an effective diffusion parameter η in the range of 0.060 to 1.0;
[0023] The geometric tortuosity τ and the effective diffusion parameter η were determined by computer-assisted three-dimensional reconstruction of focused ion beam scanning electron microscopy (FIB-SEM) analysis using an image analysis algorithm.
[0024] According to the present invention, the geometric tortuosity τ and the effective diffusion parameter η are determined using computer-assisted 3D reconstruction of focused ion beam scanning electron microscopy (FIB-SEM) analysis using image analysis algorithms. This method is believed to be more meaningful in determining τ and η than phenomenological methods such as mercury porosimetry. Mercury porosimetry is based on static, equilibrium measurements, which are less meaningful for determining structural parameters related to dynamic transport processes. The following describes methods for determining the geometric tortuosity τ and the effective diffusion parameter η.
[0025] The kinetics of diffusive mass transfer within spatially bounded porous bodies depends on various considerations, including (i) the intrinsic transport parameters of the fluid to be transported, such as the molecular diffusion coefficient under the operating conditions, and (ii) the porous structure of the solid, which determines the possible transport pathways.
[0026] The process of diffusive molecular transport in a coherent gas phase (i.e., without transport paths restricted by porous solids) is driven by spatial gradients in the fugacity (or concentration in the case of ideal gases) of chemical compounds and is typically described by Fick's first law:
[0027]
[0028] Where J represents the flow rate of the molecular compound, is the fugacity gradient of the compound that acts as the driving force for transport, is the molecular diffusion coefficient. In the case of diffusion transport in porous solids, such as solid catalysts, the effective diffusion coefficient is defined as to correct for the limited transport paths caused by the porous structure of the solid compared to the unimpeded transport in the coherent (bulk) gas phase. According to most scientific literature, this effective diffusion coefficient can be defined as (JJ Kane et al., Carbon 136 (2018) 369-379):
[0029]
[0030] Where ε represents the solid's porosity, τ is the solid's pore tortuosity, and σ is the solid's pore contraction. Tortuosity is an inherent property of porous solids, typically defined as the ratio of the length of a possible flow path through the pore structure to the straight-line distance between the ends of that path. By definition, τ assumes a value no less than 1.
[0031] Pore contraction σ is another intrinsic property of porous solids and is generally defined as the ratio of the cross-sectional area of the flow path at its narrowest point (i.e., the point of smallest cross-sectional area) to the cross-sectional area of the flow path at its widest point (i.e., the point of largest cross-sectional area). Based on this generally accepted definition adopted here, σ takes values ranging from 0 to 1, where 0 is a contraction value for a pore that is blocked at a certain point along the flow path and 1 is a contraction value for a pore that has a constant cross-sectional area along the entire flow path, such as a cylindrical pore.
[0032] Therefore, the effective diffusion parameter (η) is defined as follows:
[0033]
[0034] Describes the extent to which molecular diffusion through a given porous solid is restricted compared to molecular diffusion in a continuous gas phase under otherwise identical conditions of temperature, pressure, and fugacity gradient. Based on its definition, the parameter η takes values in the range of 0 to 1. Solid porous bodies with higher values of η have higher pore diffusion mass transfer rates.
[0035] The following equation 4 establishes the relationship between the porosity, pore size, and specific surface area of a porous solid:
[0036]
[0037] where A is the mass specific surface area, f is an arbitrary shape factor that takes into account the variance of the true pore cross section compared to the cylindrical pore cross section, and ρ sk Defines the density of the solid framework of a porous solid that defines the pores.
[0038] Porosity is the proportion of the total volume of a porous solid that corresponds to voids. With regard to the measurement of fluid transport through a porous solid, the definition is usually limited to the volume of voids that penetrate to the outer surface of the solid (which is connected).
[0039] Porosity can be determined by various experimental methods known in the art, including:
[0040] (i) Gas physical adsorption,
[0041] (ii) mercury porosimetry,
[0042] (iii) hydrothermal porosimetry or cryoprosimetry and
[0043] (iv) Direct quantification from computer-assisted three-dimensional reconstruction of the pore structure of the solid using image analysis algorithms.
[0044] Three-dimensional reconstruction of the pore structure of a solid can be obtained by a number of tomographic imaging methods. These include x-ray computed microtomography (micro-CT), electron tomography (ET), focused ion beam scanning electron microscopy (FIB-SEM) tomography, and nuclear spin resonance (NMR) tomography. The recorded (raw) tomogram is typically composed of a series of consistent parallelepiped (usually cubic) information volumes or voxels that together represent the structure of the depicted material. Each voxel is assigned an x, y, z coordinate corresponding to its geometric center in 3D space, and a grayscale value (e.g., 0 is pure black and 255 is pure white) containing information about the composition of the depicted material at that particular voxel position. In order to ensure that the depicted volume is representative and the structural parameters determined therefrom are highly accurate, it is preferred that a sample volume with a side length of at least 10 times the median pore size of the material, preferably at least 15 times the median pore size of the material, and more preferably at least 20 times the median pore size of the material be reconstructed in three dimensions. Furthermore, in this regard it is preferred to use imaging parameters which result in a side length of the elemental information unit (voxel) being at most 1 / 10 times the median pore size value of the material, preferably at most 1 / 20 times the median pore size value of the material, and more preferably at most 1 / 50 times the median pore size value of the material.
[0045] Image analysis methods are often used to extract structural information about porous solids from the corresponding tomograms. This analysis typically begins with a segmentation of the original tomogram. This involves assigning different phases to all voxels in the reconstructed tomogram based on their individual grayscale contrast values: a phase with hollow pores and a phase with solid pore walls.
[0046] Segmentation methods known in the art are based on, for example, the watershed algorithm described in E. Dougherty (ed.), Mathematical morphology in image processing, Chapter 12, pp. 433-481, Marcel Dekker, 1993, and A. Bieniek, A. Moga, Pattern Recognition (2000) 33, Issue 6, 907-916, or the contrast mask region-based convolutional neural network algorithms described in He, K. et al., Proceedings of the IEEE International Conference on Computer Vision (2017) 2961-2969. The porosity of a solid can be calculated as the ratio of the total volume of the voxels assigned to the hollow pore phase to the total volume of all voxels in the tomogram.
[0047] To facilitate the segmentation of tomograms and increase their accuracy, i.e., to improve the demarcation of interfaces between different phases in a single tomogram, various methods are used in the field to amplify the contrast differences at these boundaries without altering the structure of the sample material. Interfaces between different phases in a single tomogram are, for example, interfaces between the solid framework and the hollow pores in porous materials.
[0048] One known method involves depositing heavy metal contrast agents, such as compounds of tungsten (W), rhenium (Re), or osmium (Os), as a coating on the surface of a solid base skeleton. Another known method involves finely distributing metals or alloys in the form of metal nanoparticles on the surface of the solid base skeleton. To this end, we propose a simplified and reliable method involving FIB-SEM analysis of silver-containing epoxidation catalyst bodies (i.e., aluminum oxide supports with silver deposited thereon) and mathematically removing the silver during image analysis to examine the pore structure of the underlying aluminum oxide support.
[0049] In FIB-SEM tomography, the sample to be examined is often impregnated with a resin, such as epoxy resin, in order to remove background signals from underlying layers during SEM imaging. Such resin impregnation thus facilitates image segmentation.
[0050] Figures 1 to 3 Shown is an exemplary surface-rendered 3D FIB-SEM tomogram of a 10 μm x 10 μm x 10 μm cubic volume fraction of a porous metal-Al 2 O 3 supported catalyst obtained after segmentation and analysis.
[0051] Pore tortuosity is an important topological parameter used to describe porous solids. In formal terms, this parameter describes how the allowed flow path differs from a straight line due to the fact that the transmission is restricted by the porous solid. There are several known methods in the professional field for determining the pore tortuosity of porous solids. As described in Yang, K. et al., Transp. Porous Media (2019) 1-19, the magnitude of the tortuosity value depends on the procedure used to determine it. Methods known in the professional field for determining the tortuosity of porous solids include the following:
[0052] (i) Determination of diffusion tortuosity by measuring the diffusivity of non-reactive compounds through porous solids (Van Brakel, J., Heertjes, P., Int. J. Heat Mass Transf. (1974) 17(9), 1093–1103);
[0053] (ii) Determination of electrical tortuosity by measuring the effective conductivity of an electrolyte fluid surrounded by a porous solid (Landesfeind, J. et al., J. Electrochem. Soc. (2016) 163(7), A1373-A1387);
[0054] (iii) hydraulic tortuosity by measuring the permeability of a fluid transported through a porous solid under a pressure gradient (Clennell, MB, Geol. Soc. London, Spec. Publ. (1997) 122(1), 299–344);
[0055] (iv) Geometric tortuosity is defined as the ratio between the effective transport path length (geodesic length) and the straight line (Euclidean length) in the macroscopic flow direction and can be determined with the help of image analysis algorithms applied to computer-assisted three-dimensional reconstructions of the pore structure of solids, such as segmented tomographs.
[0056] Known algorithms for determining geometric tortuosity from computer-aided three-dimensional reconstruction of the pore structure of a solid include direct shortest path search methods as described, for example, in Stenzel, O. et al., AICHE J. (2016) 62(5), 1834-1843 and Cecen, A. et al., J. Electrochem. Soc. (2012) 159(3), B299-B307, skeleton shortest path search methods as described in Lindquist, WB et al., J. Geophys. Res. Solid Earth (1996) 101(B4), 8297-8310 and Al-Raoush, RI, Madhoun, IT, Powder Technol. (2017) 320, 99-107, skeleton shortest path search methods as described in Hassouna, MS, Farag, AA, IEEE Trans. Pattern Anal. Mach. Intell. (2007) 29(9), 1563-1574 and , PS et al., J. Microsc. (2011) 244(1), 45-58 and the pore centroid method as described in Gostovic, D., Electrochem. Solid-State Lett. (2007) 10(12), B214-B217 and Smith, J. et al., Solid State Ionics (2009) 180(1), 90-98.
[0057] Pore contraction is another important topological parameter used to describe porous solids. In formal terms, this parameter describes the cross-sectional variation through the transport path. Contraction is typically defined as the ratio of the cross-sectional area of the narrowest section (neck) along the flow path to the cross-sectional area of the widest section (pore). According to this definition adopted here, pore contraction takes a value in the range of 0 to 1. Alternative definitions can be found in the literature, such as, for example, Holzer, L. et al.; J Mater Sci (2013) 48: 2934-2952. In another commonly used definition, Petersen defines contraction as the ratio of the cross-sectional area of the widest section (pore) along the flow path to the cross-sectional area of the narrowest section (neck). (Petersen, EE (1958), Diffusion in a Pore of Varying Cross Section. AIChE J., 4: 343-345). According to this definition not adopted here, contraction takes a value greater than or equal to 1.
[0058] Information about the narrowest pore necks and widest pore segments along the permeation path can be inferred using methods known in the art, such as mercury intrusion at a constant rate, as described in Gao, H., Li, T. & Yang, L., J Petrol Explor Prod Technol 6, 309-318 (2016). Alternatively, pore and neck sizes can be determined using image analysis algorithms applied to computer-assisted three-dimensional reconstruction of the pore structure of solids.
[0059] There are various algorithms known in the field for determining information about necks and pore diameters. These algorithms typically rely on modeling the solid's 3D pore structure using a pore network model (PNM). A PNM is a virtual representation of the solid's porosity, consisting of generally spherical pore bodies and cylindrical pore contractions of varying sizes, which are interconnected in space as needed to simulate all the local geometric and topological properties of a real pore system in the solid.
[0060] There are various methods for constructing PNMs from three-dimensional reconstructions of the pore structure of a solid, such as segmented tomograms. These include grain-based models as described in Bryant, SL, King, PR, Mellor, DW, Transp. Porous Media (1993) 11(1), 53–70 and Pilotti, M. Transp. Porous Media (2000) 41(3), 359–364, particle-based models as described in Lindquist, WB et al., J. Geophys. Res. Solid Earth (2000) 105(B9), 21509–21527 and Jiang, Z. et al., Water The medial axis algorithm described in Resour. Res. (2007) 43(12), and the maximum sphere algorithm as described in Al-Kharusi, AS, Blunt, MJ, J. Pet. Sci. Eng. (2007) 56(4), 219–231 and Dong, H., Blunt, MJ, Phys. Rev. E (2009) 80(3), 036307.
[0061] There are various software packages available to allow those skilled in the art to determine structural parameters such as porosity, tortuosity and shrinkage by applying the above-mentioned and alternative algorithms to three-dimensional tomographic reconstructions of the pore structure of a solid. These include FIJI- 、 、 、 and available plugins and functionality extensions for that purpose.
[0062] As is apparent from Equation 3, an increase in the porosity ε or the pore contraction ε or both parameters and a decrease in the pore tortuosity τ increases the effective diffusion coefficient through the porous solid and thus increases the diffusion mass transfer rate through the pores.
[0063] As described, computer-assisted three-dimensional reconstructions analyzed by focused ion beam scanning electron microscopy (FIB-SEM) were used to determine the geometric tortuosity τ and the effective diffusion parameter η of the porous catalyst support shaped body by image analysis algorithms. More specifically, the pore tortuosity was determined by image analysis of segmented FIB-SEM tomograms of the catalyst obtained by dispersing silver on the support, applying a centroid path algorithm as described in Gostovic, D. et al., Journal of the American Ceramic Society (2011) 94: 620-627 to the set of tomogram voxels corresponding to the pores. The effective diffusion parameter η was determined as the porosity ε of the material multiplied by the pore contraction σ of the material multiplied by τ –2 wherein the porosity of the material is determined as the proportion of the total voxels corresponding to pores in the segmented tomogram; wherein the pore shrinkage is determined as the square of the ratio between the average diameter of all necks and the average diameter of all pores in a pore network model of the material; wherein the pore network model of the material is determined by applying a computer algorithm to a set of voxels corresponding to the pores, the computer algorithm combining a 3D chamfer distance transform, a watershed operation, and a numerical reconstruction; wherein the algorithm is adjusted so that it treats connected voxels as voxels having at least one common vertex and a contrast factor marker for H maximum is adjusted to 2, as described in E. Bretagne (2018) Mineralogical Limitations for X-Ray Tomography of Crystalline Cumulate Rocks, Durham University, and 2020.1-XPore (ThermoScientific).
[0064] The porous catalyst support shaped body has a geometric tortuosity τ in the range of 1.0 to 2.0. The porous catalyst support shaped body preferably has a geometric tortuosity τ in the range of 1.0 to 1.75, more preferably in the range of 1.0 to 1.50, in particular in the range of 1.0 to 1.30. The porous catalyst support shaped body typically has a geometric tortuosity τ of at least 1.05 or at least 1.1.
[0065] The porous catalyst support shaped body has an effective diffusion parameter η in the range of 0.060 to 1.0, preferably in the range of 0.065 to 1.0, in particular in the range of 0.070 to 1.0. The porous catalyst support shaped body typically has an effective diffusion parameter η of 0.8 or less, or 0.5 or less, or 0.2 or less.
[0066] The porous catalyst support shaped body has a total pore volume, as determined by mercury porosimetry, in the range of 0.5 to 2.0 mL / g. The porous catalyst support shaped body preferably has a total pore volume in the range of 0.5 to 1.2 mL / g, more preferably in the range of 0.5 to 1.0 mL / g, and in particular in the range of 0.5 to 0.8 mL / g. A lower total pore volume can lead to a lower absorption rate of the metal impregnation solution and thus lower catalyst activity. A higher total pore volume can lead to a lower density in the packing tube and, therefore, to lower catalyst activity.
[0067] Total pore volume is determined by mercury porosimetry. Mercury porosimetry is performed by applying controlled pressure to a sample immersed in mercury. Due to its high contact angle, mercury requires external pressure to penetrate the pores of the material. The level of pressure required to penetrate the pores is inversely proportional to the pore size. The larger the pores, the lower the pressure required to penetrate. The mercury porosimeter uses the obtained pressure-intrusion data to determine the volume and pore size distribution using the Washburn equation.
[0068] Mercury porosimetry can be performed using an AutoPore V 9600 mercury porosimeter from Micrometrics (contact angle 140 degrees, Hg surface tension 485 dynes / cm, maximum head pressure 61,000 psia). Unless otherwise indicated, porosity is determined according to DIN 66133.
[0069] The porous catalyst support shaped body preferably has a density in the filling tube greater than 450g / L. The density in the filling tube is understood to mean the density per liter of a cylindrical tube filled with a support having an internal diameter of 39mm. The density in the filling tube can be measured by the following method.
[0070] The porous catalyst support shaped body preferably has a density in the range of 450g / L to 1000g / L, preferably in the range of 480g / L to 800g / L, more preferably in the range of 500g / L to 700g / L, especially in the range of 520g / L to 650g / L in the filling pipe. The lower density in the filling pipe causes the catalyst activity to decrease. The higher density in the filling pipe can cause the catalyst consumption per unit reactor volume to be undesirably high, or causes the pressure drop to be disadvantageously high, which causes the energy consumption in the process (for example typical ethylene oxide process) of operation under the gas recirculation mode to rise.
[0071] The porous catalyst support shaped body can be obtained by the following method, wherein
[0072] i) providing a precursor material comprising, based on inorganic solid content,
[0073] - at least 50% by weight of a transition alumina having a loose bulk density of at most 600 g / L, a pore volume of at least 0.6 mL / g and an average pore size of at least 15 nm; and
[0074] - up to 30% by weight of hydrated aluminum oxide;
[0075] ii) shaping the precursor material into a shaped body; and
[0076] iii) calcining the shaped body to obtain a porous catalyst support shaped body.
[0077] Alpha-alumina formed from transition aluminas has a vermicular structure, meaning it lacks a well-defined particle structure and has extended porosity. It typically has a much finer crystal size than the preformed alpha-alumina particles without internal porosity used in the production of catalyst supports according to the prior art. This is believed to result in a porous matrix with less tortuous and convoluted channels.
[0078] The precursor material comprises, based on the inorganic solids content, at least 50 wt.-% transition alumina. Preferably, the precursor material comprises, based on the inorganic solids content, at least 60 wt.-%, more preferably at least 70 wt.-% transition alumina, such as at least 80 wt.-% or at least 90 wt.-%, especially 95 to 100 wt.-%.
[0079] The term "transitional alumina" is understood to mean an alumina comprising a metastable alumina phase, such as a gamma-, delta-, eta-, theta-, kappa- or chi-alumina phase. The transitional alumina preferably comprises at least 80% by weight, preferably at least 90% by weight, more preferably at least 95% by weight, such as from 95 to 100% by weight, of a phase selected from gamma-alumina, delta-alumina and / or theta-alumina, based on the total weight of the transitional alumina.
[0080] Transition aluminas are typically in powder form. Transition aluminas are commercially available and can be obtained by thermal dehydration of hydrated aluminum compounds, particularly aluminum hydroxide and aluminum oxyhydroxides. Suitable hydrated aluminum compounds include naturally occurring and synthetic compounds such as aluminum trihydroxide (Al(OH)3), such as gibbsite, bayerite, and nordstrandite, or aluminum oxymonohydroxides (AlOOH), such as boehmite, pseudoboehmite, and diaspore.
[0081] The gradual dehydration of hydrated aluminum compounds causes the crystal lattice to rearrange. For example, boehmite can be converted to gamma-alumina at approximately 450°C, gamma-alumina to delta-alumina at approximately 750°C, and delta-alumina to theta-alumina at approximately 1,000°C. When heated to 1,000°C, transition alumina is converted to alpha-alumina.
[0082] It is assumed that the morphological properties of the transitional aluminas thus obtained depend mainly on the morphological properties of the hydrated aluminum compounds used to prepare them. Accordingly, Busca, “The Surface of Transitional Aluminas: A Critical Review”, Catalysis Today, 226 (2014), 2-13, describes that aluminas derived from different pseudo-boehmite have different pore volumes and pore size distributions, although the pseudo-boehmite has a similar surface area (160-200 m 2 / g).
[0083] In a preferred embodiment, the transition alumina comprises non-platelet crystals. The term "non-platelet" refers to any shape other than platelet-shaped, for example, an elongated shape such as a rod or needle, or a form having approximately the same size in all three spatial directions. In a preferred embodiment, the transition alumina comprises non-platelet-shaped crystals, for example, rod-shaped crystals as described, for example, in WO 2010 / 068332 A1, or block-shaped crystals as described, for example, in Busca, "The Surface of Transitional Aluminas: A Critical Review", Catalysis Today, 226 (2014), 2-13, see Figure 2 c, 2d and 2e with Figure 2 Comparison of a, 2b and 2f. Preferably, the average crystal size of the transition alumina as determined from the XRD pattern by the Scherrer equation is at least 5 nm, more preferably at least 7 nm, especially at least 10 nm.
[0084] Various synthesis methods for obtaining crystalline boehmite-type aluminum oxides having high pore volume and high surface area and high thermal stability are known, for example, from WO 00 / 09445 A2, WO 01 / 02297 A2, WO 2005 / 014482 A2 and WO 2016 / 022709 A1. WO 2016 / 022709 A1 describes, for example, aluminum oxides having pore volume of 115 to 166 Average pore size, 250 to 350 kg / m 3 The bulk density and 0.8 to 1.1m 3 / g of pore volume of boehmite alumina, which is prepared by precipitation of basic aluminum salts with acidic alumina salts at controlled pH and temperature. Particularly suitable transition aluminas are those made by heat treatment of these boehmite aluminas and having the properties defined in the present claims.
[0085] Before heat treatment, the hydrated aluminum compound can be washed, for example, with demineralized water to reduce the impurity content and to obtain high-purity transition alumina. For example, according to Chen et al., J. Solid State Chem., 265 (2018), 237 to 243, crystalline boehmite obtained from gibbsite by a hydrothermal method is preferably washed before heat treatment.
[0086] High-purity transition aluminas are preferred to limit the amount of impurities, such as sodium or silicon, in the catalyst support. High-purity transition aluminas can be obtained, for example, by the so-called Ziegler process (also sometimes referred to as the ALFOL process) and its variants, as described in Busca, "The Surface of Transitional Aluminas: A Critical Review," in Catalysis Today, 226 (2014), 2-13. Other processes based on the precipitation of aluminates, such as sodium aluminate, tend to produce transition aluminas with relatively high levels of impurities, such as sodium.
[0087] The transition alumina used in the present invention preferably has a total content of alkali metals, such as sodium and potassium, of up to 1,500 ppm, more preferably up to 600 ppm, and especially from 10 ppm to 200 ppm, based on the total weight of the transition alumina. Various washing methods are known for reducing the alkali metal content of transition aluminas and / or catalyst supports derived therefrom. Washing can include washing with alkali, acid, water, or other liquids.
[0088] US 2,411,807 A describes reducing the sodium oxide content of precipitated alumina by washing with a solution containing hydrofluoric acid and another acid. WO 03 / 086624 A1 describes pretreating a support with an aqueous lithium salt solution to remove sodium ions from the support surface. US 3,859,426 A describes purifying refractory oxides such as aluminum oxide and zirconium dioxide by repeated washing with hot deionized water. WO 2019 / 039930 describes a method for purifying aluminum oxide in which metallic impurities are removed by extraction with alcohol.
[0089] In addition to the alkali metals, it is also preferred to control the amount of other naturally occurring impurities.
[0090] The transition alumina used in the present invention preferably has a total content of alkaline earth metals, such as calcium and magnesium, of at most 2000 ppm, more preferably at most 600 ppm, especially at most 400 ppm, based on the total weight of the transition alumina.
[0091] The transition alumina used in the present invention preferably has a silicon content of at most 10 000 ppm, more preferably at most 2000 ppm, in particular at most 700 ppm, based on the total weight of the transition alumina.
[0092] The transition alumina used in the present invention preferably has an iron content of at most 1000 ppm, more preferably at most 600 ppm, in particular at most 300 ppm, based on the total weight of the transition alumina.
[0093] The transition alumina used in the present invention preferably has a content of metals other than those mentioned above, such as titanium, zinc, zirconium and lanthanum, of at most 1000 ppm, more preferably at most 400 ppm, in particular at most 100 ppm, based on the total weight of the transition alumina.
[0094] The transition alumina has a loose bulk density of at most 600 g / L. The term "loose bulk density" is understood to mean the density "on loose introduction" or "on free-flowing introduction". "Loose bulk density" is therefore different from "tapped density", in which a specified series of mechanical impacts is used and generally a higher density is achieved. The loose bulk density can be determined by pouring the transition alumina into a graduated cylinder, suitably via a funnel, making sure not to move or shake the cylinder. Determine the volume and weight of the transition alumina. The bulk density is determined by dividing the weight in grams by the volume in litres.
[0095] A low loose bulk density may indicate high porosity and high surface area. The transition alumina preferably has a loose bulk density of 50 to 600 g / L, preferably 100 to 550 g / L, more preferably 150 to 500 g / L, especially 200 to 500 g / L or 200 to 450 g / L.
[0096] The transition alumina has a pore volume of at least 0.6 mL / g. The transition alumina preferably has a pore volume of 0.6 to 2.0 mL / g or 0.65 to 2.0 mL / g, more preferably 0.7 to 1.8 mL / g, especially 0.8 to 1.6 mL / g.
[0097] The transition alumina has a median pore diameter of at least 15 nm. The term "median pore diameter" is used herein to denote the median pore diameter based on surface area, i.e., the median pore diameter (area) value is the pore diameter at the 50th percentile of the cumulative surface area curve. The transition alumina preferably has a median pore diameter of 15 to 500 nm, more preferably 20 to 450 nm, especially 20 to 300 nm, for example 20 to 200 nm.
[0098] Mercury porosimetry and nitrogen adsorption are commonly used to characterize the pore structure of porous materials because they allow the determination of porosity and pore size distribution in a single step. These two techniques are based on different physical interactions and optimally cover a specific range of pore sizes.
[0099] In many cases, nitrogen adsorption constitutes a sufficiently accurate determination method, especially for relatively small pores. It is therefore possible to determine the pore volume and median pore diameter values of transition aluminas by nitrogen adsorption. However, nitrogen adsorption may not adequately describe larger pores.
[0100] Nitrogen adsorption measurements can be carried out with the aid of a Micrometrics ASAP 2420. Unless otherwise indicated, nitrogen porosity is determined in accordance with DIN 66134. Analysis of pore size and pore volume according to Barrett-Joyner-Halenda (BJH) is performed to obtain the total pore volume ("cumulative pore volume from BJH desorption") and the median pore size value ("average pore size from BJH desorption").
[0101] Mercury porosimetry can be performed using a Micrometrics AutoPore V 9600 mercury porosimeter (contact angle 140 degrees, Hg surface tension 485 dynes / cm, maximum head pressure 61,000 psia). For total pore volume and median pore diameter values of transition aluminas, data from the pore size range of 3 nm to 1 μm are used.
[0102] To ensure adequate accuracy, the reported pore volume and median pore size values for transition aluminas are from nitrogen adsorption when the median pore size value from mercury porosimetry is less than 50 nm; or, the reported pore volume and median pore size values for transition aluminas are from mercury porosimetry when the median pore size value from mercury porosimetry is 50 nm or greater.
[0103] In order to avoid falsification of the results, nitrogen adsorption measurements and mercury porosimetry should be performed on samples that have been treated in such a way as to remove physically adsorbed species, such as water, from the sample. Suitable methods are described below.
[0104] The BET surface area of the transition alumina can vary within a relatively wide range and can be adjusted by varying the conditions of thermal dehydration of the hydrated aluminum compound used to obtain the transition alumina. The transition alumina preferably has a BET surface area of 20 to 200 m 2 / g, more preferably 50 to 200m 2 / g or 50 to 150m 2 The BET surface area of 100 nm is 100 nm. The BET surface area is determined in accordance with DIN ISO 9277 by means of nitrogen physical adsorption at 77 K, unless otherwise indicated. The terms "BET surface area" and "surface area" are used synonymously herein, unless otherwise indicated.
[0105] Suitable transition aluminas are commercially available. In some cases, such commercially available transition aluminas are classified as "medium porosity aluminas" or particularly "high porosity aluminas". Suitable transition aluminas are, for example, TH and TM series of products, and Versal VGL series of products from UOP.
[0106] Transition alumina can be used in its commercial ("unground") form. This commercial form of alumina comprises single particles or agglomerates (secondary particles) of particles (primary particles). For example, the average (secondary) particle size (e.g., D 50 ) of 25 μm may contain submicron primary particles. As referred to herein, the median particle size (D 50 ) is understood to refer to the particle size of the secondary alumina particles (D 50 ).
[0107] Unground transition alumina powders typically have a D of 10 to 100 μm, preferably 20 to 50 μm. 50Particle size. In addition, it is possible to use transition alumina that has been subjected to a grinding operation to reduce the particles to the desired particle size. Suitably, the transition alumina can be ground in the presence of a liquid; it is preferably ground in the form of a suspension. Alternatively, the grinding can be carried out by dry ball milling. The ground transition alumina powder typically has a D of 0.5 to 8 μm, preferably 1 to 5 μm. 50 Particle size. The particle size of transition alumina can be measured by laser diffraction particle size measurement equipment, such as the Malvern Mastersizer 2000, using water as the dispersion medium. The method involves dispersing the particles by ultrasonic treatment, which causes the secondary particles to break into primary particles. This ultrasonic treatment is continued until no D is observed. 50 Further changes in the values, for example after 3 minutes of sonication.
[0108] In a preferred embodiment, the transition alumina comprises at least 50% by weight, more preferably 60% to 90% by weight, of transition alumina having an average particle size of 10 to 100 μm, especially 20 to 50 μm, based on the total weight of the transition alumina. The transition alumina may comprise, for example, up to 50% by weight, more preferably 10% to 40% by weight, of transition alumina having an average particle size of 0.5 to 8 μm, preferably 1 to 5 μm, based on the total weight of the transition alumina.
[0109] The precursor material comprises up to 30% by weight of hydrated aluminum oxide, based on the inorganic solids content. The precursor material preferably comprises from 1% to 30% by weight of hydrated aluminum oxide, based on the inorganic solids content, more preferably from 1% to 25% by weight, in particular from 1% to 20% by weight, for example from 3% to 18% by weight.
[0110] The term "hydrated alumina" relates to hydrated aluminum compounds as described above, in particular aluminum hydroxide and aluminum oxyhydroxides. A discussion of the nomenclature of transition aluminas can be found in K. Wefers and C. Misra, "Oxides and Hydroxides of Aluminum", Alcoa Laboratories, 1987. Suitable hydrated aluminum compounds include naturally occurring and synthetic compounds, such as aluminum trihydroxide (Al(OH)3), such as gibbsite, bayerite and nordstrandite, or aluminum oxymonohydroxides (AlOOH), such as boehmite, pseudoboehmite and diaspore.
[0111] The hydrated aluminum oxide preferably comprises boehmite and / or pseudo-boehmite. In a preferred embodiment, the total amount of boehmite and pseudo-boehmite constitutes at least 80% by weight of the hydrated aluminum oxide, more preferably at least 90% by weight, especially at least 95% by weight, such as from 95% to 100% by weight. In a particularly preferred embodiment, the amount of boehmite constitutes at least 80% by weight of the hydrated aluminum oxide, more preferably at least 90% by weight, especially at least 95% by weight, such as from 95% to 100% by weight.
[0112] Suitable hydrated aluminas are commercially available and include those from Sasol. Series of products, preferred TH and TM series products, and from UOP series of products.
[0113] Without wishing to be bound by this speculation, it is speculated that the presence of hydrated alumina improves the mechanical stability of the support. In particular, it is speculated that highly dispersible nano-sized hydrated alumina suitable for colloidal applications, such as from Sasol or The boehmite series has a high binding capacity and is particularly effective in improving the mechanical stability of the support. Generally speaking, the use of such nano-scale highly dispersed hydrated aluminum oxides to improve mechanical stability enables a relatively low BET surface area to be achieved under given calcination conditions.
[0114] The hydrated aluminum oxide may be partially or completely replaced by a suitable alternative aluminum compound, in which case the mechanical stability of the support is substantially maintained. Such suitable alternative aluminum compounds include aluminum alkoxides, such as aluminum ethoxide and aluminum isopropoxide, aluminum nitrate, aluminum acetate and aluminum acetylacetonate.
[0115] The precursor material may contain a liquid. The presence, type, and amount of the liquid may be selected based on the desired processing properties of the precursor material. For example, the presence of the liquid may be desirable to obtain a formable precursor material.
[0116] The liquid is typically selected from water, especially deionized water, and / or an aqueous solution containing a soluble and / or dispersible compound selected from salts such as ammonium acetate and ammonium carbonate; acids such as formic acid, nitric acid, acetic acid, and citric acid; bases such as ammonia, triethylamine, and methylamine; surfactants such as triethanolamine, poloxamers, fatty acid esters, and alkyl polyglucosides; submicron-sized particles including metal oxides such as silicon dioxide, titanium dioxide, and zirconium dioxide; clays; and / or polymer particles such as polystyrene and polyacrylates. The liquid is preferably water, especially deionized water. The typical amount of liquid varies in the range of 10% to 60% by weight, based on the inorganic solids content of the precursor material.
[0117] The precursor material may contain additional components, which may be processing aids or specifically introduced to adjust the physical properties of the final catalyst support. Additional components include pore-forming materials, lubricants, organic binders and / or inorganic binders.
[0118] The precursor material may contain organic materials such as pore forming materials, lubricants, and organic binders in a total amount of 1.0 wt% to 60 wt%, preferably 3 wt% to 50 wt%, based on the total weight of the precursor material.
[0119] The precursor material may contain the lubricant and the organic binder in an amount of 1.0 wt% to 10 wt%, preferably 3 wt% to 8 wt%, based on the total weight of the precursor material.
[0120] Pore-forming materials can be used to provide additional and / or wider pores in the support. The additional pore volume of the wider pores can also advantageously allow for more efficient impregnation of the support during catalyst production. The pore-forming material is preferably substantially completely removed during heat treatment of the shaped body. Pore formation can be achieved by various mechanisms, such as combustion (i.e., oxidation) in the presence of oxygen, decomposition, sublimation, or volatilization.
[0121] Suitable pore-forming materials include
[0122] - thermally decomposable materials, such as oxalic acid, malonic acid, ammonium carbonate or ammonium bicarbonate;
[0123] - burnt materials, for example thermally combustible biomaterials, such as gum arabic, sawdust and ground material, in particular ground nut shells, such as ground pecan shells, cashew shells, walnut shells or hazelnut shells; and / or
[0124] -Organic polymers, e.g.
[0125] - polysaccharides, such as starch, rubber, cellulose and cellulose derivatives, including substituted celluloses, such as methylcellulose, ethylcellulose and carboxyethylcellulose, and cellulose ethers;
[0126] - polyolefins, such as polyethylene and polypropylene;
[0127] - aromatic polymers, such as polystyrene;
[0128] - polycarbonates, such as poly(propylene carbonate); and
[0129] - lignin;
[0130] -Carbonaceous materials, such as
[0131] -graphite;
[0132] - powdered carbon-containing compounds, such as coke, or activated carbon powder; and
[0133] - Milled or unmilled carbon fibers.
[0134] Thermally decomposable materials, such as oxalic acid, malonic acid, ammonium carbonate, or ammonium bicarbonate, decompose upon heat treatment and break down into smaller, volatile molecules that may or may not be flammable. For example, malonic acid decomposes primarily into acetic acid and carbon dioxide upon heat treatment. Such thermally decomposable materials can offer certain advantages in industrial processes because they are generally available from industrial sources with a certain purity so that they do not introduce impurities into the carrier.
[0135] To avoid the formation of an explosive atmosphere, calcination of shaped bodies made of thermally decomposable material is preferably carried out in an atmosphere with a reduced oxygen content, for example, up to 10% by volume or up to 5% by volume. When thermal decomposition is carried out at relatively low temperatures, the process can be reliably controlled to a temperature well below the ignition temperature of potentially combustible molecules formed during the decomposition of the decomposable material. This allows for safe thermal treatment even in the presence of relatively high oxygen concentrations in the atmosphere within the thermal treatment apparatus. In this case, an air atmosphere may be used.
[0136] Suitable lubricants include
[0137] -graphite;
[0138] - petrolatum, mineral oil or grease;
[0139] fatty acids, such as stearic acid or palmitic acid; fatty acid salts, for example stearates, such as potassium stearate, magnesium stearate and aluminium stearate, or palmitates, such as potassium palmitate, magnesium palmitate and aluminium palmitate; fatty acid derivatives, such as esters of fatty acids, in particular esters of saturated fatty acids, such as stearic acid esters, such as methyl stearate and ethyl stearate; and / or
[0140] - moldable organic solids, for example waxes, such as paraffin and cetyl palmitate.
[0141] Preferably, the lubricant does not introduce any inorganic impurities into the catalyst support. Among the above lubricants, preferred are graphite, stearic acid, aluminum stearate and combinations thereof.
[0142] Organic binders, sometimes also referred to as "temporary binders," can be used to improve the formability of the precursor material and maintain the integrity of the "green," or unfired, phase, in which the mixture is formed into a shaped body. The organic binder is preferably substantially completely removed during the heat treatment of the shaped body.
[0143] Suitable organic binders include
[0144] - polyvinyl lactam polymers, such as polyvinyl pyrrolidone, or vinyl pyrrolidone copolymers, such as vinyl pyrrolidone-vinyl acetate copolymers;
[0145] - alcohols, in particular polyols such as glycols or glycerol; and / or
[0146] - polyalkylene glycols, for example polyethylene glycol.
[0147] Advantageously, the pore-forming materials and processing aids, such as organic binders and lubricants, have a low ash content. The term "ash content" is understood to mean the unburned fraction remaining after the organic material is burned in air at high temperatures, i.e., after heat treatment of the shaped body. The ash content is preferably less than 0.1% by weight, based on the total weight of the organic material.
[0148] Furthermore, pore-forming materials and processing aids, such as organic binders and lubricants, preferably do not form any significant amounts of additional volatile, combustible components, such as carbon monoxide, ammonia, or combustible organic compounds, during the thermal treatment of the shaped body, i.e., during thermal decomposition or combustion. Excessive amounts of volatile organic components can create an explosive atmosphere. It is preferable to use an appropriate safety concept for the combustion or decomposition process steps.
[0149] Inorganic binders are permanent binders that facilitate sufficient bonding of the alumina particles and enhance the mechanical stability of the α-alumina molded body. Inorganic binders include those that form only alumina upon firing. For the purposes of this application, these inorganic binders are referred to as intrinsic inorganic binders. Such intrinsic inorganic binders include hydrated alumina, as described above.
[0150] In contrast, extrinsic inorganic binders do not form only alumina when calcined. Suitable extrinsic inorganic binders are all inorganic species conventionally used in the professional field, for example silicon-containing species, such as silicon dioxide or silicates, including clays, such as kaolinite, or metal hydroxides, metal carbonates, metal nitrates, metal acetates or metal oxides such as zirconium dioxide, titanium dioxide or alkali metal oxides. Since extrinsic inorganic binders introduce impurities that may have an adverse effect on catalyst performance, they are preferably present in a controlled amount. The precursor material preferably comprises 0.0 wt % to 5.0 wt %, preferably 0.05 wt % to 1.0 wt % of extrinsic inorganic binder based on the inorganic solids content of the precursor material. In a preferred embodiment, the precursor material does not comprise extrinsic inorganic binder.
[0151] The precursor material is generally provided by dry mixing of its components and optionally subsequent addition of a liquid.The precursor material can be shaped into shaped bodies by extrusion, tableting, granulation, casting, shaping or microextrusion, in particular by extrusion or tableting.
[0152] The size and shape of the shaped body and thus the catalyst are selected so that the catalyst obtained from the shaped body can be properly filled in the reactor tube. The catalyst obtained from the shaped body suitable for the catalyst of the present invention is preferably used in reactor tubes having a length of 6 to 14 m and an internal diameter of 20 mm to 50 mm. Generally speaking, the support consists of individual components with a maximum extension of 3 to 20 mm, such as 4 to 15 mm, and in particular 5 to 12 mm. The maximum extension is understood to mean the longest straight line between two points on the outer circumference of the support.
[0153] The shape of the shaped body is particularly not limited and can have any technically possible shape, which depends, for example, on the shaping process. The support can be, for example, a solid extrudate or a hollow extrudate, such as a hollow cylinder. In another embodiment, the support can be characterized by a multi-lobed structure. A multi-lobed structure is understood to mean a cylindrical structure having a plurality of cavities, such as grooves or trenches, extending along the circumference of the cylinder and along the height of the cylinder. Typically, these cavities are arranged substantially equidistantly around the circumference of the cylinder.
[0154] The support preferably has the shape of a solid extrudate, such as a pellet or cylinder, or a hollow extrudate, such as a hollow cylinder. In a preferred embodiment, the shaped body is formed by extrusion, such as microextrusion. In this case, the precursor material suitably comprises a liquid, especially water, to form a formable precursor material.
[0155] In a preferred embodiment, the extrusion comprises introducing at least one solid component into a mixing device before the addition of the liquid. Preference is given to using a roller-based mixer (Mix-Muller, H-roller) or a horizontal mixer, e.g. Mixer (from Gebrüder The shaping of the extrudable paste used to produce the precursor material can be monitored and controlled with reference to data from the mixing device reflecting the desired properties.
[0156] The precursor material is usually extruded through a shaped orifice. The cross section of the shaped orifice is selected according to the desired geometry of the shaped body.
[0157] The shaped orifice for extrusion may comprise a die and a mandrel, in which case the die substantially determines the outer surface area of the shaped body, while the mandrel substantially determines the shape, size and position of any channels. Suitable extrusion tools are described, for example, in WO 2019 / 219892 A1.
[0158] The geometry of the shape of the shaped body is defined by the geometry of the extrusion apparatus through which the precursor material is extruded. Typically, the geometry of the shape of the extrudate differs slightly from the geometry of the extrusion apparatus, but generally shares the geometric properties described above. The absolute dimensions of the shape are typically slightly smaller than those of the extrudate due to the high temperatures required to form α-alumina and the shrinkage of the extrudate as it cools. The extent of this shrinkage depends on the temperature used during calcination and the composition of the shaped body. Therefore, the size of the shaped orifice used for extrusion should generally be adjusted to account for extrudate shrinkage during subsequent calcination.
[0159] If the shaped body comprises a plurality of channels, the axes of the channels generally run in parallel. However, the shaped bodies may be slightly bent or twisted around their z-axis (height). The shape of the cross section of the channel may be slightly different from the desired ideal geometric form described above. In the case of a large number of shaped bodies, the individual channels of a few shaped catalyst bodies may be closed. Typically, due to the production process, the end faces of the shaped catalyst bodies in the xy plane are more or less uneven, rather than smooth. The height of the shaped body (the length of the shaped body in the z direction) is generally not exactly the same for all shaped bodies, but rather constitutes a certain distribution having an average height as an arithmetic mean.
[0160] The extrudate is preferably cut into the desired length while still wet. The extrudate is preferably cut at an angle substantially perpendicular to its circumference. To reduce undesirable deviations from the geometry of the extrusion apparatus, the extrudate may alternatively be cut at an angle of up to 30°, for example 10° or 20°, relative to the angle perpendicular to the circumference of the extrudate.
[0161] Geometric deviations, such as those that occur during the extrusion process and / or during the further processing of the extrudate, such as during the cutting step, can in principle also occur in the porous catalyst support according to the invention without significantly reducing the advantageous effect of its pore structure. It is clear to those skilled in the art that, due to the inherent inaccuracies of all production methods to a certain extent, a perfect geometric form cannot be achieved at all.
[0162] In another embodiment, the precursor material is formed into a shaped body by means of a microextrusion method as described in WO 2019 / 072597 A1.
[0163] In another embodiment, the precursor material is formed into a shaped body using a gel casting method as described in WO 2020 / 053563 A1.
[0164] In a further embodiment, the precursor material is formed into a formed body by tableting. In this case, the precursor material does not usually contain any liquid. Tableting is a press agglomeration method. Powdered or previously agglomerated bulk material is introduced into a pressing die with a die between two punches, compacted and formed into a solid compact by uniaxial compression. This operation is divided into four parts: metering introduction, compaction (elastic deformation), plastic deformation and discharge. For example, tableting is carried out on a rotary press or an eccentric press.
[0165] If necessary, the upper punch and / or the lower punch may have protruding pins to form internal channels. It is also possible to equip the pressing punch with multiple movable pins, so that the punch can be equipped with four pins to produce a molded body with four holes (channels), for example. A typical configuration of such a tool can be found in, for example, US 8,865,614 B2.
[0166] The compression force during tableting influences the compaction of the bulk material. In practice, it has been found to be suitable to control the lateral compressive strength of the porous catalyst support by selecting the appropriate compression force and checking this by random sampling. In the present invention, the lateral compressive strength is the force required to rupture the porous catalyst support between two parallel plates, with the two flat, parallel end faces of the catalyst support at right angles to the parallel plates.
[0167] For tableting, it is generally advantageous to use lubricants, in particular those mentioned above. In order to improve the tableting properties, it is possible to use a pre-granulation and / or sieving step. For pre-granulation, it is possible to use a roll compressor, for example from Fitzpatrick Further information on tableting, in particular on pre-granulation, sieving, lubricants and tools can be found in WO 2010 / 000720 A2.
[0168] Before calcination, the shaped body may be dried, especially when the precursor material contains a liquid. Drying is suitably carried out at a temperature of 20 to 400° C., especially 30 to 300° C., for example 70 to 150° C. Drying is generally carried out for a period of up to 100 hours, preferably 0.5 to 30 hours, more preferably 1 to 16 hours.
[0169] Drying can be carried out in any atmosphere, for example in an oxygen-containing atmosphere, such as air, nitrogen or helium, or a mixture thereof, preferably in air. Drying is usually carried out in an oven. The type of oven is not particularly limited. For example, a stationary air circulation oven, a rotary cylindrical oven or a tunnel oven can be used. Heat can be supplied directly and / or indirectly.
[0170] Preferably, the drying step uses flue gases (exhaust gases) from the combustion process at a suitable temperature. The flue gases can be used in diluted or undiluted form to achieve direct heating and remove evaporated water and other components released from the shaped bodies. Typically, the exhaust gases are passed through an oven as described above. In another preferred embodiment, the exhaust gases from the calcination process step are used for direct heating.
[0171] Drying and calcining can be carried out sequentially in separate apparatuses and can be carried out in a batch or continuous process. Intermediate cooling may be used. In another embodiment, drying and calcining are carried out in the same apparatus. In batch processes, it is possible to use a time-resolved temperature ramp (program). In continuous processes, it is possible to use a spatially resolved temperature ramp (program), for example, when the shaped body is continuously passed through regions (zones) of different temperatures.
[0172] Heat integration measures known from the prior art are preferably used to improve energy efficiency. For example, it is possible to use the relatively hot exhaust gas from one process step or stage to heat the feed gas, equipment, or shaped bodies in a different process step or stage directly (mixing) or indirectly (heat exchanger). It is also possible to use heat integration to cool the relatively hot exhaust gas stream before further processing or application.
[0173] The shaped body is calcined to obtain a porous catalyst support.The calcination temperature and time are therefore sufficient to convert at least a portion of the transition alumina into alpha-alumina, which means to convert at least a portion of the metastable alumina phase in the transition alumina into alpha-alumina.
[0174] Typically, calcination is carried out at a temperature of at least 1100° C., such as at least 1300° C., preferably at least 1350° C., more preferably at least 1400° C., and especially at least 1450° C. Calcination is preferably carried out at an absolute pressure of 0.5 to 35 bar, especially 0.9 to 1.1 bar, for example at atmospheric pressure (approximately 1013 mbar). The total duration of heating is typically 0.5 to 100 hours, preferably 2 to 20 hours.
[0175] Calcination is usually carried out in a furnace. The type of furnace is not particularly limited. For example, furnaces such as stationary air circulation furnaces, rotary furnaces or tunnel furnaces, or combustion furnaces such as rotary combustion furnaces or tunnel combustion furnaces, in particular roller hearth furnaces, can be used.
[0176] Calcination can be carried out in any atmosphere, for example in an oxygen-containing atmosphere, such as air, nitrogen or helium, or mixtures thereof. Preferably, in particular when the shaped body contains thermally decomposable material or burn-off material, calcination is carried out at least partially or completely in an oxidizing atmosphere, such as in an oxygen-containing atmosphere, such as air.
[0177] As mentioned above, pore-forming materials and processing aids, such as organic binders and lubricants, preferably do not form any significant amounts of additional volatile combustible components, such as carbon monoxide or combustible organic compounds, during calcination of the shaped body. An explosive atmosphere can also be avoided by limiting the oxygen concentration in the atmosphere during calcination, for example, to an oxygen concentration below the limiting oxygen concentration (LOC) of the additional combustible components. The LOC, also known as the minimum oxygen concentration (MOC), is the limiting oxygen concentration below which combustion is not possible.
[0178] It is possible to appropriately use a recycle stream of lean air or gas with a limited oxygen content together with a stream for oxygen enrichment, which also compensates for the gas purge stream. In another approach, it is possible to avoid an explosive atmosphere by limiting the rate of formation of additional combustible components. The rate of formation of additional combustible components can be limited by gradually heating to the calcination temperature or by heating in steps. In the case of gradual heating, it is appropriate to maintain the temperature at approximately the combustion temperature for several hours and then heat to a temperature of 1000° C. In a continuous calcination process, it is also possible to control the feed rate of the shaped bodies to the calcination device, such as a furnace, in order to limit the rate of formation of additional combustible components.
[0179] Depending on the nature of the pore forming material, lubricant, organic binder and gas composition, it is possible to use exhaust gas treatment to purify the exhaust gases obtained during calcination. Preferably, it is possible to use acidic or alkaline absorbers, flare or catalytic combustion, DeNOx treatment or a combination thereof for exhaust gas treatment.
[0180] Gradual heating is preferred. In the case of gradual heating, the shaped body can be placed in a highly clean and inert refractory combustion capsule, which moves through a furnace having several heating zones, for example 2 to 8 or 2 to 5 heating zones. The inert refractory fuel capsule can be made of α-alumina or corundum, especially α-alumina.
[0181] The porous catalyst support usually has a thickness of 0.5 to 5.0 μm. 2 The porous catalyst support preferably has a BET surface area in the range of 1.0 to 4.0 m 2 / g, more preferably 1.5 to 3.0 m 2 / g, especially 1.7 to 2.5m 2 / g, such as 1.8 to 2.2 m 2 The BET surface area is in the range of 1000 Å / g.
[0182] The pore volume of the porous catalyst support contained in pores with a diameter in the range of 0.1 to 1 μm, as determined by mercury porosimetry, is generally at least 40% of the total pore volume. The pore volume of the porous catalyst support contained in pores with a diameter in the range of 0.1 to 1 μm is at least 50% of the total pore volume, more preferably at least 55% of the total pore volume, in particular at least 60% of the total pore volume, such as at least 65% or at least 70% of the total pore volume. The pore volume contained in pores with a diameter in the range of 0.1 to 1 μm in the porous catalyst support is generally preferably 40% to 99%, more preferably 45% to 99%, and in particular 50% to 97% of the total pore volume.
[0183] The porous catalyst support generally has a ratio r of at most 0.50 of the pore volume present in pores with a diameter in the range of greater than 1 to 10 μm to the pore volume present in pores with a diameter in the range of 0.1 to 1 μm. pv Ratio r pv It is preferably in the range of 0.0 to 0.45, more preferably 0.0 to 0.40 or 0.0 to 0.35.
[0184] The porous support comprises at least 85 wt%, preferably at least 90 wt%, more preferably at least 95 wt%, and especially at least 97.5 wt% of α-alumina, based on the total weight of the support. The amount of α-alumina can be determined, for example, by x-ray diffraction analysis.
[0185] In one embodiment, the porous catalyst support shaped body has
[0186] - 0.5 to 5.0m 2 BET surface area in the range of 1000 nm / g;
[0187] - a total pore volume of at least 0.5 mL / g as measured by mercury porosimetry; and
[0188] - at least 40% of the total pore volume is present in pores with a diameter in the range of 0.1 to 1 μm, as determined by mercury porosimetry;
[0189] The ratio r of the pore volume present in pores with diameters in the range of greater than 1 to 10 μm to the pore volume present in pores with diameters in the range of 0.1 to 1 μm is pv The maximum is 0.50.
[0190] In a preferred embodiment, the porous support is in the form of a single shaped body, such as the form described above. The porous catalyst support is preferably in the form of a single shaped body having an outer surface, a first side (lateral face), a second side and at least one internal channel extending from the first side to the second side.
[0191] Geometric surface area SA of the catalyst support geo The geometric volume V of the catalyst support geo The ratio (SA geo / V geo ) is preferably at least 1.1 mm –1 and up to 10mm –1 . Preferably, SA geo With V geo The ratio is 1.15mm –1 Up to 5.0mm –1 within the range of 1.2 mm, more preferably 1.2 mm –1 Up to 2.0mm –1 Geometric surface area SA geo and geometric volume V geo is derived from the external macroscopic dimensions of the porous catalyst support, taking into account the cross-sectional area, height and, if appropriate, the number of internal channels. In other words, the geometric volume V of the catalyst support geo It is the volume of a solid body with the same external dimensions minus the volume occupied by the channels. Geometric surface area SA geo The surface area of the channel is also composed of the circumferential area, the first and second end faces, and optionally, the surface area of the channel. The first and second end faces are respectively the surface enclosed by the circumference of the end faces minus the cross-sectional area of the channel. The surface area of the channel is the surface of the channel lining.
[0192] SA in the preferred range geo With V geo The ratio of enables the reaction gases to better contact with the catalyst surface, which promotes the conversion of reactants and limits internal diffusion phenomena, thereby improving the reaction selectivity.
[0193] The porous catalyst support shaped body preferably does not have any washcoat particles or a washcoat layer on its surface in order to sufficiently maintain the porosity of the uncoated support.
[0194] The porous catalyst support shaped body may contain impurities such as sodium, potassium, magnesium, calcium, silicon, iron, titanium and / or zirconium. These impurities may be introduced via components of the precursor material, in particular inorganic binders or additives for improving mechanical stability. In one embodiment, the porous catalyst support shaped body comprises, based on the total weight of the support,
[0195] - a maximum total of 1500 ppmw of sodium and potassium;
[0196] - up to 2000 ppmw calcium;
[0197] - up to 1000 ppmw magnesium;
[0198] - up to 10 000 ppmw of silicon;
[0199] - up to 1000 ppmw of titanium;
[0200] - up to 1000 ppmw iron; and / or
[0201] - Up to 10 000 ppmw zirconium.
[0202] Low sodium content is preferred to prevent segregation of the loaded metal and to avoid any change in the loaded composition.
[0203] The present invention also relates to shaped catalyst bodies for preparing ethylene oxide by selective gas-phase oxidation (epoxidation) of ethylene, ie epoxidation catalysts, comprising at least 15% by weight of silver, based on the total weight of the shaped catalyst body, deposited on a porous catalyst support as described above.
[0204] The shaped catalyst bodies generally comprise from 15% to 70% by weight of silver, preferably from 20% to 60% by weight of silver, more preferably from 25% to 50% by weight or from 30% to 50% by weight of silver, based on the total weight of the shaped catalyst bodies. A silver content within this range enables a favorable balance between the conversion rate caused by the respective shaped catalyst body and the cost-effectiveness of producing the shaped catalyst bodies.
[0205] In addition to silver, the shaped catalyst body may also contain one or more promoter species. A promoter species refers to a component that improves one or more catalytic properties of the catalyst compared to a catalyst without the component. The promoter species may be any of those species known in the art to improve the catalytic properties of silver catalysts. Examples of catalytic properties are operating ability (resistance to runaway), selectivity, activity, conversion, and catalyst life.
[0206] The shaped catalyst body may contain a transition metal or a mixture of two or more transition metals in an amount effective as a promoter. Suitable transition metals can be, for example, elements from Group IIIB (scandium), Group IVB (titanium), Group VB (vanadium), Group VIB (chromium), Group VIIB (manganese), Group VIIIB (iron, cobalt, nickel), Group IB (copper), and Group IIB (zinc), of the Periodic Table of the Elements, and combinations thereof. Typically, the transition metal is an early transition metal, i.e., from Group IIIB, IVB, VB, or VIB, such as hafnium, yttrium, molybdenum, tungsten, rhenium, chromium, titanium, zirconium, vanadium, tantalum, niobium, or a combination thereof. In one embodiment, the transition metal promoter is present in a total amount of 150 ppm to 5000 ppm, typically 225 ppm to 4000 ppm, and most typically 300 ppm to 3000 ppm, relative to the gross weight of the shaped catalyst body, expressed as metal.
[0207] Of the listed transition metal promoters, rhenium (Re) is a particularly effective promoter for ethylene epoxidation catalysts having high selectivity. The rhenium component of the shaped catalyst body may be in any suitable form, but is typically one or more rhenium-containing compounds (e.g., rhenium oxide) or complexes.
[0208] In some embodiments, the shaped catalyst body may contain an alkali metal or a mixture of two or more alkali metals in an amount effective as a promoter. Suitable alkali metal promoters are, for example, lithium, sodium, potassium, rubidium, cesium, or a combination thereof. The amount of alkali metal, such as potassium, is typically 50 ppm to 5000 ppm, preferably 300 ppm to 2500 ppm, more preferably 500 ppm to 1500 ppm, based on the alkali metal, relative to the total weight of the shaped catalyst body. The amount of alkali metal depends on the amount of alkali metal introduced by the porous catalyst support and the amount of alkali metal introduced by the impregnation solution described below.
[0209] Particularly preferred are combinations of heavy alkali metals such as cesium (Cs) or rubidium (Rb) and light alkali metals such as lithium (Li), sodium (Na) and potassium (K).
[0210] The shaped catalyst body may also contain a Group IIA alkaline earth metal or a mixture of two or more Group IIA alkaline earth metals. Suitable alkaline earth metal promoters are, for example, beryllium, magnesium, calcium, strontium, and barium, or combinations thereof. The alkaline earth metal promoter may be used in an amount similar to that of the alkali metal or transition metal promoter.
[0211] The shaped catalyst body may also contain a main group element or a mixture of two or more main group elements in an amount effective as a promoter. Suitable main group elements include any element from Group IIIA (boron group) to Group VIIA (halogen group) of the Periodic Table of the Elements. For example, the shaped catalyst body may contain sulfur, phosphorus, boron, halogen (e.g., fluorine), gallium, or a combination thereof in an amount effective as a promoter.
[0212] The shaped catalyst body may also contain a rare earth metal or a mixture of two or more rare earth metals in an amount effective as a promoter. Rare earth metals include any element with an atomic number from 57 to 103. Some examples of these elements are lanthanum (La), cerium (Ce), and samarium (Sm). The amount of rare earth metal promoter used may be similar to the amount of transition metal promoter.
[0213] The present invention also relates to a method for producing a shaped catalyst body as described above, wherein
[0214] a) impregnating a porous catalyst support shaped body as described above with a silver impregnation solution, preferably under reduced pressure; and optionally subjecting the impregnated porous catalyst support shaped body to drying; and
[0215] b) subjecting the impregnated porous catalyst support shaped body to a heat treatment;
[0216] wherein steps a) and b) are optionally repeated.
[0217] It goes without saying that all embodiments of the shaped catalyst bodies also apply, if appropriate, to the process for producing the shaped catalyst bodies.
[0218] To obtain a shaped catalyst body having a high silver content, steps i) and ii) can be repeated multiple times. In this case, it is presumed that the catalyst intermediate obtained after the first (or subsequent up to the penultimate) impregnation / calcination cycle contains a portion of the total target Ag and / or promoter concentration. This catalyst intermediate is then impregnated again with the silver impregnation solution and calcined to obtain the target Ag and / or promoter concentration.
[0219] It is possible to use any silver impregnation solution known in the art to be suitable for impregnating refractory supports. The silver impregnation solution typically comprises a silver carboxylate, such as silver oxalate, or a combination of a silver carboxylate and oxalic acid, in the presence of an amine complexing agent, such as C1-C 10- in the presence of an alkylenediamine, especially ethylenediamine. Suitable impregnation solutions are described in EP 0 716 884 A2, EP 1 115 486 A1, EP 1 613 428 A1, US 4,731,350 A, WO 2004 / 094055 A2, WO 2009 / 029419 A1, WO 2015 / 095508 A1, US 4,356,312 A, US 5,187,140 A, US 4,908,343 A, US 5,504,053 A and WO 2014 / 105770 A1. A discussion of suitable silver impregnation solutions can also be found in Kunz, C. et al., On the Nature of Crystals Precipitating from Aqueous Silver Ethylenediamine Oxalate Complex Solutions., Z. Anorg. Allg. Chem., 2021, 647, DOI: 10.1002 / zaac.202100079.
[0220] During the heat treatment, the liquid components of the silver impregnation solution evaporate, causing silver compounds containing silver ions to precipitate from the solution and deposit on the porous support. At least a portion of the deposited silver ions is subsequently converted to metallic silver upon further heating. Based on the total molar amount of silver in the impregnated porous catalyst support, preferably at least 70 mol % of the silver compound is present, more preferably at least 90 mol %, even more preferably at least 95 mol %, and especially at least 99.5 mol % or at least 99.9 mol %, i.e., substantially all of the silver ions. The amount of silver ions converted to metallic silver can be determined, for example, by means of an X-ray diffraction pattern (XRD).
[0221] Heat treatment may also be referred to as a calcination process. Any calcination process known in the art for this purpose may be used. Suitable examples of calcination methods are described in US 5,504,052 A, US 5,646,087 A, US 7,553,795 A, US 8,378,129 A, US 8,546,297 A, US 2014 / 0187417 A1, EP 1 893 331 A1 or WO 2012 / 140614 A1. The heat treatment may be carried out in a continuous process or with at least partial recirculation of the calcination gas.
[0222] The heat treatment is typically carried out in a furnace. The type of furnace is not particularly limited. For example, a stationary air circulation furnace, a rotary furnace, or a tunnel furnace may be used. In one embodiment, the heat treatment comprises passing a stream of heated gas through the impregnated body. The duration of the heat treatment is typically in the range of 5 minutes to 20 hours, preferably 5 minutes to 30 minutes.
[0223] The heat treatment temperature is generally in the range of 200 to 800° C., preferably 210 to 650° C., more preferably 220 to 500° C., and in particular 220 to 350° C. The heating rate in the temperature range of 40 to 200° C. is preferably at least 20 K / min, more preferably at least 25 K / min, for example at least 30 K / min. High heating rates can be achieved by passing the heating gas through the impregnated refractory support or the impregnated catalyst intermediate at a high gas flow rate.
[0224] Suitable throughputs of the gas may be, for example, 1 to 1000 m3 per kg of impregnated material. 3 / h(STP), 10 to 1000m 3 / h(STP), 15 to 500m 3 / h(STP) or 20 to 300m 3 / h (STP) range. The term "kilogram of impregnation" is understood in a continuous process to mean the amount of impregnation (in kg / h) multiplied by the time (in hours) that the gas stream passes through the impregnation. It has been found that when the gas stream passes over a relatively large amount of impregnation, for example 15 to 150 kg of impregnation, the flow rate can be selected in the lower part of the above range, in which case the desired effect is achieved.
[0225] Directly measuring the temperature of a heated impregnated body can present practical difficulties. Therefore, when heated gas is passed through the impregnated body during heat treatment, the temperature of the heated impregnated body is considered to be the temperature of the gas immediately after the gas passes through the impregnated body. In one practical embodiment, the impregnated body is placed on a suitable surface, such as a wire braid or perforated calcining belt, and the gas temperature is measured using one or more thermocouples positioned adjacent to the side of the impregnated body opposite the side initially contacted by the gas. The thermocouples are suitably positioned close to the impregnated body, for example, at a distance of 1 to 30 mm, such as 1 to 3 mm or 15 to 20 mm.
[0226] The use of multiple thermocouples can improve the accuracy of the temperature measurement. If multiple thermocouples are used, they can be evenly distributed across the surface of the impregnated body on the wire mesh or across the width of the perforated calcining belt. The average value is taken as the gas temperature immediately after passing through the impregnated body. To heat the impregnated body to the above-mentioned temperatures, the gas typically has a temperature of 220 to 800°C, preferably 230 to 550°C, and in particular 240 to 350°C.
[0227] Gradual heating is preferred. In this case, the impregnated body is placed on a conveyor belt that moves through a furnace having several heating zones, for example 2 to 8 or 2 to 5 heating zones. The heat treatment is preferably carried out in an inert atmosphere, for example nitrogen, helium or mixtures thereof, in particular nitrogen.
[0228] The present invention further relates to a process for preparing ethylene oxide by selective gas-phase oxidation (epoxidation) of ethylene, which comprises reacting ethylene and oxygen in the presence of a shaped catalyst body as described above.
[0229] It goes without saying that all embodiments of the shaped catalyst bodies also apply, if appropriate, to the process for preparing ethylene oxide in the presence of shaped catalyst bodies.
[0230] Epoxidation can be carried out by any method known to those skilled in the art. It is possible to use any reactor that can be used in the ethylene oxide production process of the prior art, for example an externally cooled shell and tube reactor (see Ullmann's Encyclopedia of Industrial Chemistry, 5th edition, volume A-10, pages 117-135, 123-125, VCH-Verlagsgesellschaft, Weinheim 1987) or a reactor with a loose catalyst bed and cooling tubes, such as the reactor described in DE 34 14 717 A1, EP 0 082 609 A1 and EP 0 339 748 A2.
[0231] Epoxidation is preferably carried out in at least one tubular reactor, preferably in a shell and tube reactor. On an industrial scale, ethylene epoxidation is preferably carried out in a multi-tubular reactor comprising thousands of tubes. The catalyst is introduced into the tubes, which are present in a shell filled with a coolant. In commercial applications, the inner tube diameter is typically in the range of 20 to 40 mm (see, for example, US 4,921,681 A) or greater than 40 mm (see, for example, WO 2006 / 102189 A1).
[0232] To prepare ethylene oxide from ethylene and oxygen, the reaction can be carried out under conventional reaction conditions, as described, for example, in DE 25 21 906 A, EP 0 014 457 A2, DE 23 00 512 A1, EP 0 172 565 A2, DE 24 54 972 A1, EP 0 357 293 A1, EP 0 266 015 A1, EP 0 085 237 A1, EP 0 082 609 A1, and EP 0 339 748 A2. It is also possible to add an inert gas, such as nitrogen, or a gas inert under the reaction conditions, such as steam, methane, and optionally a reaction moderator, such as a halogenated hydrocarbon, such as ethyl chloride, vinyl chloride, or 1,2-dichloroethane, to the reaction gas composed of ethylene and molecular oxygen.
[0233] The oxygen content of the reaction gas is preferably within a range where an explosive gas mixture is not present. Suitable compositions of the reaction gas for producing ethylene oxide may contain, for example, 10 to 80% by volume, preferably 20 to 60% by volume, of ethylene. The oxygen content of the reaction gas is preferably within a range of not more than 10% by volume, preferably not more than 9% by volume, more preferably not more than 8% by volume, and most preferably not more than 7.5% by volume.
[0234] The reaction gas preferably contains a chlorine-containing reaction moderator, such as ethyl chloride, vinyl chloride, or 1,2-dichloroethane, in an amount of 0 to 15 ppm by weight, preferably 0.1 to 8 ppm by weight, based on the total weight of the reaction gas. The remainder of the reaction gas typically consists of hydrocarbons, such as methane, and inert gases, such as nitrogen. Furthermore, other substances, such as steam, carbon dioxide, or noble gases, may also be present in the reaction gas.
[0235] The carbon dioxide concentration in the feed (i.e., the gas mixture supplied to the reactor) generally depends on the catalyst selectivity and the efficiency of the carbon dioxide removal unit. The carbon dioxide concentration in the feed is preferably at most 3% by volume, more preferably less than 2% by volume, and especially less than 1% by volume. An exemplary carbon dioxide removal unit is described in US Pat. No. 6,452,027 B1.
[0236] Each of the above-mentioned components of the reaction mixture may optionally include small amounts of impurities. Ethylene can be used, for example, at any purity suitable for the gas-phase oxidation of the present invention. Suitable purities include, but are not limited to, polymer-grade ethylene, which typically has a purity of at least 99%, and chemical-grade ethylene, which typically has a purity of less than 95%. Impurities typically consist, inter alia, of ethane, propane, and / or propylene.
[0237] The reaction or oxidation of ethylene to ethylene oxide is typically carried out at elevated catalyst temperatures. Preference is given to catalyst temperatures in the range of 150 to 350° C., more preferably 180 to 300° C., even more preferably 190 to 280° C., and especially 200 to 280° C. The present invention therefore also provides a process as described above, wherein the oxidation is carried out at a catalyst temperature of 180 to 300° C., preferably 200 to 280° C. The catalyst temperature can be measured by thermocouples in the catalyst bed. As used herein, the catalyst temperature or the temperature of the catalyst bed is considered to be the weight-average temperature of the catalyst particles.
[0238] The reaction (oxidation) of the present invention is preferably carried out at a pressure of 5 to 30 bar. Unless otherwise indicated, all pressures herein are absolute pressures. Particularly preferably, oxidation is carried out at a pressure of 5 to 25 bar, for example 10 to 24 bar, in particular 14 to 23 bar. The present invention therefore also provides a method as described above, wherein oxidation is carried out at a pressure of 14 to 23 bar.
[0239] It has been found that the physical properties of the shaped catalyst bodies, in particular the BET surface area and pore size distribution, have a significant positive influence on the catalyst selectivity. This effect is particularly pronounced when the catalyst is operated at very high productivity (working rate), i.e., at high olefin oxide production.
[0240] The process of the present invention is preferably carried out under conditions suitable for obtaining a reaction mixture containing at least 2.3% by volume of ethylene oxide. In other words, the ethylene oxide discharge concentration (ethylene oxide concentration at the reactor outlet) is preferably at least 2.3% by volume. The ethylene oxide discharge concentration is preferably in the range of 2.5% to 4.0% by volume, more preferably in the range of 2.7% to 3.5% by volume.
[0241] The oxidation is preferably carried out in a continuous process. If the reaction is carried out continuously, the GHSV (gas hourly space velocity) is preferably in the range of 800 to 10 000 / h, more preferably in the range of 2000 to 8000 / h, even more preferably in the range of 2500 to 6000 / h, and in particular in the range of 4500 to 5500 / h, depending on the type of reactor selected, for example on the size / cross-sectional area of the reactor, the shape and size of the catalyst, the values reported being based on the catalyst volume.
[0242] In a further embodiment, the present invention also relates to a process for preparing ethylene oxide (EO) by gas phase oxidation of ethylene with oxygen as disclosed above, wherein the measured EO space-time yield is greater than 180 kg EO / (m 3 cat h), preferably greater than 200 kg EO / (m 3 cat h) If it is greater than 250kg EO / (m 3 cat h) More than 280kg EO / (m 3 cat h) or more than 300kg EO / (m 3 cat h) EO space-time yield. The measured EO space-time yield is preferably less than 500 kg EO / (m 3 cat h); EO space-time yield is more preferably less than 350kg EO / (m 3 cat h).
[0243] The preparation of ethylene oxide from ethylene and oxygen can advantageously be carried out in a circulation process. After each pass, the newly formed ethylene oxide and the by-products formed in the reaction are removed from the product gas stream. The remaining gas stream is supplemented with the required amount of ethylene, oxygen and reaction moderator and reintroduced into the reactor. The ethylene oxide can be separated from the product gas stream and worked up by conventional prior art methods (see Ullmanns et al., 1996). der industriellenChemie [Ullmann's Encyclopedia of Industrial Chemistry], 5th edition, volume A-10, pages 117-135, 123-125, VCH-Verlagsgesellschaft, Weinheim 1987).
[0244] The invention is explained in more detail by means of the accompanying drawings and the following examples.
[0245] Figure 1 Figure 2 is an exemplary surface-rendered 3D FIB-SEM tomogram of a 10 μm x 10 μm x 10 μm cubic volume of a porous metal-Al2O3 catalyst obtained after segmentation. The solid material labeled (i) corresponds to the Al2O3 skeleton, which delimits the pores labeled (ii).
[0246] Figure 2 Figure 1 is an exemplary surface-rendered 3D FIB-SEM tomogram of a 10 μm x 10 μm x 10 μm cubic volume of a porous metal-Al2O3 catalyst obtained after segmentation. The image shows only the voxels corresponding to the supported metal.
[0247] Figure 3 An exemplary illustration of the pore network model calculated from a FIB-SEM tomogram of a 10 μm x 10 μm x 10 μm cubic volume of a porous supported metal-Al2O3 catalyst. The image shows the pore regions as spheres of different volumes connected by cylindrical necks.
[0248] Figure 4 The shapes of porous α-alumina catalyst supports A and B are shown.
[0249] Figure 5 The logarithmic differential intrusion [mL / g] and the cumulative intrusion [mL / g] of the porous catalyst support A of the present invention are shown versus the pore size (pore diameter) [μm].
[0250] Figure 6The logarithmic differential intrusion amount [mL / g] and the cumulative intrusion amount [mL / g] of the porous catalyst support B (comparative example) are shown vs. the pore size (pore diameter) [μm].
[0251] Figure 7 A representative scanning electron micrograph of a cross section exposed by focused ion beam machining of comparative catalyst 2 is shown. The pores appear in black, the Al2O3 framework appears in light gray, and the supported silver particles appear as white bodies. The scale bar has a horizontal length of 2000 nanometers.
[0252] Figure 8 A representative scanning electron micrograph shows a cross-section of catalyst 1 according to the present invention exposed by machining with a focused ion beam. The pores appear in black, the Al2O3 framework appears in light gray, and the supported silver particles appear as white objects. The scale bar has a horizontal length of 2000 nanometers.
[0253] Method 1: Nitrogen adsorption
[0254] The nitrogen adsorption measurements were carried out with the aid of a Micrometrics ASAP 2420. The nitrogen porosity was determined in accordance with DIN 66134. Prior to the measurement, the samples were degassed under reduced pressure at 200° C. for 16 hours.
[0255] Method 2: Mercury porosimetry
[0256] Mercury porosimetry on shaped α-alumina catalyst support bodies was carried out using an AutoPore V 9600 mercury porosimeter from Micrometrics (contact angle 140 degrees, Hg surface tension 485 dyne / cm, maximum head pressure 61 000 psia). The mercury porosity was determined in accordance with DIN 66133.
[0257] The samples were dried at 110°C for 2 hours and degassed under reduced pressure before analysis to remove physically adsorbed species, such as moisture, from the sample surface.
[0258] Method 3: Loose Bulk Density of Powder
[0259] To determine the loose bulk density, introduce the transition alumina or hydrated alumina into a graduated cylinder via a funnel, making sure not to move or shake the cylinder. Measure the volume and weight of the transition alumina or hydrated alumina. Determine the loose bulk density by dividing the volume in milliliters by the weight in grams.
[0260] Method 4: BET surface area
[0261] The BET surface area was determined according to DIN ISO 9277 using nitrogen physical adsorption at 77 K. The surface area was determined from a 5-point BET plot. Prior to the measurement, the sample was degassed under reduced pressure at 200°C for 16 hours. In the case of shaped α-alumina support bodies, more than 4 g of sample was used due to the relatively low BET surface area.
[0262] Method 5: Density of porous catalyst support shaped bodies in the filling tube
[0263] The density in the filled tube is measured by introducing an amount of x grams of the carrier molded body into a cylindrical glass tube with an inner diameter of 39 mm until the scale indicates an internal volume of y milliliters. The glass tube is placed on a balance, and the weight increase due to the introduction of the carrier is measured as x. The density in g / L is calculated as (x / y) × 1000.
[0264] Method 6: Total Analysis of Ca, Mg, Si, Fe, K, and Na Contents in α-Alumina Supports 6A. Sample Preparation for Measurement of Ca, Mg, Si, and Fe
[0265] Approximately 100 to 200 mg (±0.1 mg error) of the support sample was weighed into a platinum crucible. 1.0 gram of lithium metaborate (LiBO2) was added. The mixture was melted in an automated melting apparatus at a temperature ramp up to 1150°C.
[0266] After cooling, the melt was dissolved in deionized water by careful heating. Subsequently, 10 ml of semi-concentrated hydrochloric acid (concentrated HCl diluted with deionized water, volume ratio 1:1, equivalent to about 6 M) was added. Finally, the solution was made up to a volume of 100 ml with deionized water.
[0267] 6B. Measurement of Ca, Mg, Si, and Fe
[0268] The Ca, Mg, Si and Fe contents were determined from the solutions described in point 6A by inductively coupled plasma-optical emission spectroscopy (ICP-OES) using a Varian Vista Pro ICP-OES.
[0269] parameter:
[0270] Wavelength [nm]: Ca 317.933
[0271] Mg 285.213
[0272] Si 251.611
[0273] Fe 238.204
[0274] Integration time: 10s
[0275] Nebulizer: conical 3mL
[0276] Atomizer pressure: 270kPa
[0277] Pump speed: 30 rpm
[0278] Calibration: External (matrix adapted standard)
[0279] 6C. Sample Preparation for K and Na Measurements
[0280] Approximately 100 to 200 mg (± 0.1 mg error) of the carrier sample is weighed into a platinum dish. Add 10 ml of a mixture of concentrated H2SO4 aqueous solution (95% to 98%) and deionized water (volume ratio 1:4) and 10 ml of hydrofluoric acid aqueous solution (40%). Place the platinum dish on a sand bath and boil until dry. After cooling the platinum dish, dissolve the residue in deionized water by careful heating. Subsequently, add 5 ml of semi-concentrated hydrochloric acid (concentrated HCl diluted with deionized water, volume ratio 1:1, equivalent to approximately 6M). Finally, the solution is supplemented to a volume of 50 ml with deionized water.
[0281] 6D. Measurement of K and Na
[0282] The amounts of K and Na were determined from the solution described in point 6C by flame atomic absorption spectrometry (F-AAS) using a Shimadzu AA-7000 F-AAS.
[0283] parameter:
[0284] Wavelength [nm]: K 766.5Na 589.0
[0285] Gas: Air / Acetylene
[0286] Gap width: 0.7nm(K) / 0.2nm(Na)
[0287] Atomizer pressure: 270kPa
[0288] Calibration: External (matrix adapted standard)
[0289] Method 7: Tomographic focused ion beam scanning electron microscopy (FIB-SEM) and tomogram analysis
[0290] Focused ion beam scanning electron microscopy (FIB-SEM) is used to measure the porosity and the pore topology of material. In an experimental manner, with a razor blade, the three-leaf or four-leaf cylinder of material is cut into small aliquots (about 2 mm). Use the ultrathin sectioning mold (pyramid-tip ultramicrotomy mold) of tapered tip to infiltrate and embed these smaller material fragments with low viscosity epoxy resin (Spurr, Merck), and resin is solidified 12 hours at 343K. Then the resin-embedded sample block is cut to size and polished in the ultrathin microtome (ReichertUltracut) with a diamond blade (Diatome), and is positioned on the SEM probe with epoxy adhesive.
[0291] Next, a conductive layer was applied to the resin-embedded sample and metal stump using a colloidal graphite suspension in isopropyl alcohol. The sample mounted on the probe was then sputter-coated with a carbon layer approximately 20 nm thick in a BAL-TEC SCD 005 coater to achieve a fully conductive connection and minimize local charging artifacts during SEM imaging. FIB-SEM experiments were performed in a Zeiss Auriga dual-beam microscope equipped with a Ga ion cannon and secondary electron and backscattered electron detectors.
[0292] In order to minimize curtaining effects, an additional metallic Pt layer (approximately 30 nm) was applied to the region of interest (ROI) with the aid of an ion cannon and metal gas injection using a dual-beam microscope. + A focused beam of ions machines the front and side channels (depth of approximately 45 μm) to expose a finely polished front area of the block to be imaged (width of approximately 30-40 μm x height of 35-45 μm). A cross-shaped fiducial mark is drawn on the upper surface of the sample next to one of the side channels to serve as a reference for automatic drift correction during FIB-SEM imaging. Next, an automatic slice & view algorithm is started to machine thin sections of nominal thickness 35-45 nm from the front of the imaging block using a FIB gun operating at an intensity of 2 nA, and an SEM micrograph of each newly exposed cross section is recorded with a secondary electron detector, while the electron gun is operated at an accelerating voltage of 1-3 kV.
[0293] The SEM micrograph set (2048 x 1536 pixels) was then processed by vertical expansion correction for compensating for the angular alignment of the machining and imaging guns in the dual-beam microscope (which formed a 54-degree angle), and a bandpass FFT filter (see, for example, Kim, D. et al. (2019), Microscopy and Microanalysis, 25 (5), 1139-1154) implemented in FIJI-ImageJ 1.53 software was used to reduce curtaining artifacts. The stacked micrographs were aligned with the help of a cross-correlation algorithm (see, for example, Yaniv Z. (2008) Rigid Registration. In: Peters T., Cleary K. (eds), Image-Guided Interventions. Springer, Boston, MA.). Finally, the stack was cut into a cubic data volume. The resulting reconstructed cube tomogram had a resolution of (20 to 23 μm) 3 The volume of the element voxel is (15 to 45nm) 3 .
[0294] To quantify the material topology, voxels in the reconstructed FIB-SEM tomograms were classified according to their contrast (greyscale) and assigned to the various subvolumes or phases, i.e. pores, alumina and supported metal, by segmentation with the aid of a marker-based 3D watershed algorithm (E. Dougherty, ed., Mathematical morphology in image processing, Chapter 12, pp. 433-481. Marcel Dekker, 1993). (ThermoScientific), the automatically identified volumes are then fine-tuned by controlled erosion expansion functions to remove artifact material “islands,” and manual thresholding is performed to correct for local grayscale gradients caused by curtaining or shadowing phenomena.
[0295] The total porosity was then determined as the proportion of the total voxels corresponding to the pores of the subvolume. The average geometric pore tortuosity was determined as the ratio between the geodesic pore distance and the Euclidean pore distance by propagating the pores of the tomogram of the subvolume through the centroid path algorithm (Gostovic, D. et al., Journal of the American Ceramic Society (2011) 94: 620-627). For two independent tomograms of each sample, four quadrants of equal size and the entire volume were considered, respectively, to assess the statistical uncertainty associated with the average geometric pore tortuosity.
[0296] For the analysis of pore shrinkage, An algorithm combining a chamfer distance transform, a 3D watershed operation, and numerical reconstruction implemented in 2020.1-XPore (ThermoScientific) (E. Bretagne (2018) Mineralogical Limitations for X-Ray Tomography of Crystalline Cumulate Rocks, Durham University) is applied to the subvolume pores to produce a label field that separates the individual pores (locally wider segments of the 3D subvolume pores connected by narrower segments or necks). The algorithm is adjusted so that voxels considered to be connected are those with at least one common vertex, and the contrast factor marker for the maximum value of H is set to 2. Thus, a pore network model is constructed, i.e., a three-dimensional model of spherical pores connected by cylindrical necks, which corresponds to the real pore space network. The shrinkage parameter is defined as the square of the ratio between the average diameter of all necks in the pore network model and the average diameter of all pores.
[0297] For the silver-supported catalyst, the porosity, pore tortuosity, pore contraction, and effective diffusion parameters of the alumina support were quantified after first assigning the tomogram voxels that had been segmented into the supported metal to the set of voxels corresponding to the subvolume pores (thus mathematically removing the supported metal from the surface area of the alumina support material).
[0298] Production of porous α-alumina catalyst carrier
[0299] The properties of the transition alumina and hydrated alumina used to produce the porous α-alumina catalyst support are listed in Table 1. The transition alumina and hydrated alumina were obtained from Sasol ( and ).
[0300] The transition alumina and hydrated alumina according to Table 1 were mixed to obtain a powder mixture. A processing aid (from Unilever) was added. and glycerol from Sigma-Aldrich) and water were added to the powder mixture. MCC Spheres 200 (microcrystalline cellulose, from JRS Pharma) was added to the mixture. Subsequently, water was further added to obtain a formable precursor material. The total amounts of all components are listed in Table 2.
[0301] The moldable precursor material is mixed to homogeneity by means of a roller-based mixer (Mix-Muller) and then extruded using a ram extruder to obtain a molded body. Figure 4 The extrudates were dried overnight at 110°C (approximately 16 hours) and then heat treated in a muffle furnace at 600°C for 2 hours and then at elevated temperatures (1475°C for Support A and 1430°C for Support B) for 4 hours. The heat treatment was performed under air.
[0302] The dimensions of the dried applied layer were determined using calipers. The diameter of the circumscribed circle of the cross section at right angles to the support height was 11.6 cm. The term "circumscribed circle" refers to the smallest circle that completely encloses the trilobal cross section. The diameter of the inscribed circle of the cross section at right angles to the support height was 5.3 cm. The term "inscribed circle" refers to the largest possible circle that can be drawn within the trilobal cross section. The central channel had a diameter of 1.92 cm. The three outer channels had a diameter of 1.46 cm.
[0303] The resulting shaped support bodies A and B had an α-alumina content of greater than 98% by weight and a Na, K, Mg, and Ca content of less than 100 ppm. The Fe content in both supports was 200 ppm. The Si content in support A was 100 ppm. The Si content in support B was 200 ppm.
[0304] The two shaped support bodies A and B had a density in the packing tube of 550 g / L.
[0305] Table 3 shows the physical properties of the carrier S prepared according to Table 2. Figure 5 and 6 The logarithmic differential intrusion amount and the cumulative intrusion amount of the supports prepared according to Table 2 are shown versus the pore size (pore diameter).
[0306] Table 1
[0307]
[0308] *Puralox products are transition aluminas, i.e. boehmite, made from Pural products
[0309] **Measured by nitrogen adsorption
[0310] Table 2
[0311]
[0312] *Comparative Example
[0313] Table 3
[0314]
[0315] *Comparative Example
[0316] **Measured by mercury porosimetry
[0317] ***r pv = the ratio of the pore volume present in pores with diameters in the range of greater than 1 to 10 μm to the pore volume present in pores with diameters in the range of 0.1 to 1 μm
[0318] Catalyst manufacturing
[0319] The shaped catalyst bodies were made by impregnating supports A and B with the silver impregnation solution. The catalyst compositions are shown in Table 4 below. The silver content is reported as a percentage based on the total weight of the catalyst. The amount of promoter is reported as parts per million (ppm) based on the total weight of the catalyst.
[0320] Table 4: Catalyst composition (Ag content is reported as a percentage by weight of the total catalyst; the amount of promoter is reported in ppm based on the weight of the total catalyst)
[0321]
[0322] Calculate the amount of silver
[0323] **K ADD This refers to the amount of potassium applied during the impregnation process and does not include the amount of potassium present in the alumina support before impregnation.
[0324] **Comparative Example
[0325] 1. Production of silver complex solution
[0326] A silver complex solution was produced according to Preparation Example 1 of WO 2019 / 154863 A1. The silver complex solution had a density of 1.529 g / mL, a silver content of 29.3% by weight, and a potassium content of 90 ppm.
[0327] 2. Production of catalyst intermediates
[0328] In each case, 100.0 g of carrier A (intermediate 1.1) or 100.4 g of carrier B (intermediate 1.2) were introduced into a 2-liter glass flask. The flask was connected to a rotary evaporator, which was under a vacuum pressure of 80 mbar. The rotary evaporator was set to rotate at 30 rpm. Under a vacuum pressure of 80 mbar, 76.55 g (intermediate 1.1) or 76.86 g (intermediate 1.2) of the silver complex solution prepared in step 2.1 were added to carrier A (intermediate 1.1) or carrier B (intermediate 1.2) over 15 minutes. After the addition of the silver complex solution, rotary evaporation was continued under reduced pressure for another 15 minutes. The impregnated carriers were then left in the apparatus at room temperature (approximately 25° C.) and atmospheric pressure for 1 hour, carefully mixing every 15 minutes.
[0329] The impregnated material was placed on the net in 1 to 2 layers. The net was exposed to 23m 3 (STP) / h of air stream, which was preheated to a temperature of 305 ° C. The impregnated material was heated to a temperature of 290 ° C. at a heating rate of approximately 30 K / min and then held at 290 ° C. for 8 minutes to obtain the Ag-containing intermediate according to Table 5. The temperature was measured by placing three thermocouples at a distance of 1 mm below the mesh. The catalyst was then cooled to ambient temperature by removing the catalyst intermediate from the mesh using an industrial vacuum cleaner.
[0330] Table 5: Catalyst intermediates containing Ag (Ag content is reported as a percentage by weight of the total catalyst; the amount of promoter is reported in ppmw based on the weight of the total catalyst intermediate)
[0331]
[0332]
[0333] Calculate the amount of silver
[0334] **K ADD This refers to the amount of potassium added during the impregnation process and does not include the amount of potassium present in the alumina support before impregnation.
[0335] 3. Catalyst production
[0336] 120.5 g of the Ag-containing intermediate 1.1 or 122.2 g of the Ag-containing intermediate 1.2 prepared in step 2.2 were each introduced into a 2-liter glass flask. The flask was connected to a rotary evaporator under a vacuum pressure of 80 mbar. The rotary evaporator was set to rotate at 30 rpm. For catalyst 1, 53.80 g of the silver complex solution prepared in step 2.1 were mixed with 2.16 g of promoter solution I, 2.80 g of promoter solution II, and 4.69 g of promoter solution III. For catalyst 2, 54.56 g of the silver complex solution prepared in step 2.1 were mixed with 2.19 g of promoter solution I, 2.84 g of promoter solution II, and 4.76 g of promoter solution III.
[0337] Promoter solution I was obtained by dissolving lithium nitrate (Merck, 99.995%) and ammonium sulfate (Merck, 99.4%) in deionized water to achieve a Li content of 2.85 wt.% and an S content of 0.22 wt.%. Promoter solution II was obtained by dissolving tungstic acid (HC Starck, 99.99%) in deionized water and cesium hydroxide in water (HC Starck, 50.42%) to achieve a target Cs content of 5.0 wt.% and a W content of 3.0 wt.%. Promoter solution III was obtained by dissolving ammonium perrhenate (Buss & Buss Spezialmetalle GmbH, 99.9%) in deionized water to achieve a Re content of 3.7 wt.%.
[0338] The combined impregnation solution of the silver complex solution and accelerator solutions I, II, and III was stirred for 5 minutes. The combined impregnation solution was added to each silver-containing intermediate 1.1 or 1.2 over a period of 15 minutes under a vacuum pressure of 80 mbar. After the addition of the combined impregnation solution, rotary evaporation was continued under reduced pressure for a further 15 minutes. The impregnated support was then left in the apparatus at room temperature (approximately 25° C.) and atmospheric pressure for 1 hour, being carefully mixed every 15 minutes.
[0339] Place the impregnated material on the net in 1 to 2 layers. 3 A nitrogen stream (at STP) / h (oxygen content: <20 ppm) was passed through the mesh, preheating the gas stream to a temperature of 305° C. The impregnated material was heated to a temperature of 290° C. at a heating rate of approximately 30 K / min and then held at 290° C. for 7 minutes to obtain the catalyst according to Table 4. The temperature was measured by placing three thermocouples at a distance of 1 mm below the mesh. The catalyst was subsequently cooled to ambient temperature by removing the catalyst bodies from the mesh using an industrial vacuum cleaner.
[0340] Figure 7 and 8Representative scanning electron micrographs showing cross sections exposed by machining of catalysts 1 and 2 with a focused ion beam.
[0341] Catalyst testing
[0342] The epoxidation reaction was carried out in a vertically arranged stainless steel test reactor with an internal diameter of 6 mm and a length of 2.2 m. The reactor was heated with hot oil in a heating jacket at a specific temperature. All temperatures below are based on the temperature of the hot oil. 9 grams of inert steatite spheres (0.8 to 1.1 mm) were loaded into the reactor, 26.4 grams of crushed catalyst sieved to a desired particle size of 1.0 to 1.6 mm were filled thereon, and another 29 grams of inert steatite spheres (0.8 to 1.1 mm) were refilled thereon. Inlet gas was introduced into the reactor top in a "once-through" mode of operation.
[0343] The catalyst was introduced into the reactor at a reactor temperature of 90°C, a nitrogen flow rate of 130 L (STP) / h, and a pressure of 1.5 bar absolute. The reactor temperature was then increased to 210°C at a heating rate of 50 K / h, and the catalyst was maintained in this state for 15 hours. The nitrogen flow was then replaced with a flow of 114 L (STP) / h of methane and 1.5 L (STP) / h of CO₂. The reactor was set to a pressure of 16 bar absolute. 30.4 L (STP) / h of ethylene and 0.8 L (STP) / h of a 500 ppm mixture of ethylene dichloride in methane were then added. Oxygen was then gradually introduced until a final flow rate of 6.1 L (STP) / h was reached. At this time, the inlet composition consisted of 20 vol% ethylene, 4 vol% oxygen, 1 vol% carbon dioxide, and 2.5 ppmv (parts per million by volume) of ethylene dichloride (EC) moderator, with methane used as the balance at a total gas throughput of 152.8 L (STP) / h.
[0344] The reactor temperature was increased to 225°C at a heating rate of 5 K / h and thereafter to 240°C at a heating rate of 2.5 K / h. The catalyst was maintained under these conditions for 135 hours. The EC concentration was then reduced to 2.2 ppmv, and the temperature was lowered to 225°C. The inlet gas composition was then gradually changed to 35% by volume ethylene, 7% by volume oxygen, and 1% by volume carbon dioxide, using methane as the balance and a total gas throughput of 147.9 L (STP) / h. The temperature was adjusted to achieve an ethylene oxide (EO) concentration of 3.05% in the outlet gas. The EC concentration was adjusted to optimize selectivity. The results of the catalyst testing are summarized in Table 6.
[0345] Table 6
[0346]
[0347] *Comparative Example
[0348] **Effective diffusion parameter η, determined by Equation 3
[0349] **Run time starts when oxygen is added to the ethylene-containing feed stream
[0350] The error interval corresponds to the standard error SE, which is defined as SE = s / (N) 1 / 2 , where s is the standard deviation and N is the number of evaluations, affected in the case of the parameter η by the uncertainties in porosity, shrinkage and geometric tortuosity.
[0351] It is clear that Catalyst 1 obtained from support A according to the invention has a much higher selectivity than Catalyst 2 obtained from comparative support B.
Claims
1. A porous catalyst support shaped body comprising at least 85 wt. % alpha-alumina, wherein the support has a total pore volume in the range of 0.5 to 2.0 mL / g as determined by mercury porosimetry, and a pore structure characterized by - a geometric tortuosity τ in the range of 1.0 to 2.0; and - an effective diffusion parameter η in the range of 0.060 to 1.0; The geometric tortuosity τ and the effective diffusion parameter η were determined by computer-assisted three-dimensional reconstruction of focused ion beam scanning electron microscopy analysis using an image analysis algorithm. The porous catalyst support shaped body is obtained as follows: i) providing a precursor material comprising, based on inorganic solid content, - at least 50% by weight of transition alumina having a loose bulk density of at most 600 g / L, a pore volume of at least 0.6 mL / g and a median pore diameter value of at least 15 nm; and - up to 30% by weight of hydrated aluminum oxide; ii) shaping the precursor material into a shaped body; and iii) calcining the shaped body to obtain a porous catalyst support shaped body. 2 . The porous catalyst support shaped body according to claim 1 , which has a density in the packing tube of more than 450 g / L.
3. The porous catalyst support shaped body according to claim 1 has a thickness of 0.5 to 5.0 μm. 2 The BET surface area is in the range of 1000 Å / g.
4. The porous catalyst support shaped body according to claim 2 has a thickness of 0.5 to 5.0 μm. 2 The BET surface area is in the range of 1000 Å / g.
5. The porous catalyst support shaped body according to claim 3 or 4, having a thickness of 1.5 to 3.0 m 2 The BET surface area is in the range of 1000 Å / g. 6 . The porous catalyst support shaped body according to claim 1 , wherein the transition alumina has a loose bulk density of 50 to 600 g / L and a pore volume of 0.6 to 2.0 mL / g.
7. The porous catalyst support shaped body according to claim 1, wherein the transition alumina comprises a phase selected from the group consisting of γ-alumina, δ-alumina and θ-alumina.
8. The porous catalyst support shaped body according to claim 6, wherein the transition alumina comprises a phase selected from the group consisting of γ-alumina, δ-alumina and θ-alumina.
9. The porous catalyst support shaped body according to claim 7 or 8, wherein the transitional alumina comprises a phase selected from the group consisting of gamma-alumina and delta-alumina.
10. The porous catalyst support shaped body according to claim 1, wherein the hydrated aluminum oxide comprises boehmite and / or pseudoboehmite.
11. The porous catalyst support shaped body according to claim 10, wherein the precursor material further comprises a pore-forming material, a lubricant, an organic binder and / or an inorganic binder.
12. The porous catalyst support shaped body according to claim 11, wherein the precursor material is shaped into a shaped body by extrusion, tableting, pelletizing, casting, molding or microextrusion.
13. The porous catalyst support shaped body according to claim 11, wherein the precursor material is shaped into the shaped body by extrusion or tableting.
14. The porous catalyst support shaped body according to claim 12, wherein the calcination is carried out at a temperature of at least 1100°C.
15. The porous catalyst support shaped body according to claim 14, wherein the calcination is carried out at a temperature of at least 1300°C.
16. The porous catalyst support shaped body according to claim 14, wherein the calcination is carried out at a temperature of at least 1400°C.
17. The porous catalyst support shaped body according to claim 14, wherein the calcination is carried out at a temperature of at least 1450°C.
18. A shaped catalyst body for the preparation of ethylene oxide by gas-phase oxidation of ethylene, comprising at least 15% by weight of silver, based on the total weight of the catalyst, deposited on a porous catalyst support shaped body according to any one of claims 1 to 17.
19. A process for producing a shaped catalyst body according to claim 18, wherein a) impregnating the porous catalyst support shaped body according to any one of claims 1 to 17 with a silver impregnation solution; and optionally subjecting the impregnated porous catalyst support shaped body to drying; and b) subjecting the impregnated porous catalyst support shaped body to a heat treatment; wherein steps a) and b) are optionally repeated.
20. The method according to claim 19, wherein the porous catalyst support shaped body is impregnated with the silver impregnation solution under reduced pressure.
21. A process for preparing ethylene oxide by gas-phase oxidation of ethylene, which comprises reacting ethylene and oxygen in the presence of a shaped catalyst body according to claim 18.
Citation Information
Patent Citations
DE117135A
silver catalysts, processes for their preparation and their use
DE2300512A1
Silver olefin oxidation catalysts - supported on specified carriers and promoted esp. with barium
DE2454972A1
silver catalyst and its use
DE2521906A1
Process and reactor for carrying out exothermic catalytic reactions
DE3414717A1